Developing apparatus, cleaning method, process cartridge, and electrophotographic image forming apparatus
Patent Information
- Application Number
- JP2022146783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-09-15
AI Technical Summary
【0010】 本開示によれば、キズの発生とフィルミングの発生とを極めて高い次元で抑制できる現像ローラを有する現像装置であっても、高温高湿環境下に放置されることによる現像ローラピッチの帯画像の発生を抑制し、高耐久かつ高品位な画像を得ることができる現像装置が得られる。また、本開示によれば、上記現像ローラの外表面をクリーニングする方法が得られる。また、本開示の他の態様によれば、高品位な電子写真画像を安定して出力できるプロセスカートリッジ及び電子写真画像形成装置が得られる。
Smart Images

Figure 0007933597000016 
Figure 0007933597000017 
Figure 0007933597000018
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to a developing device, a cleaning method, a process cartridge, and an electrophotographic image forming apparatus. BACKGROUND ART
[0002] A developing device of an electrophotographic image forming apparatus (hereinafter also referred to as "electrophotographic apparatus") according to one aspect includes a developing container that stores toner, a toner supply roller for supplying toner to a developing roller, a toner regulating member for regulating the supplied toner on the developing roller to an appropriate amount, and a developing roller for conveying the toner and developing an electrostatic latent image. In order to enhance customer value, developing devices for such electrophotographic apparatuses are required to be capable of obtaining high-quality images. Furthermore, with the growing environmental awareness represented by SDGs in recent years, there is a demand for highly durable developing devices that can be used for a much longer service life or can be used repeatedly than ever before.
[0003] One major factor that determines the durability of a developing device is the occurrence of scratches on the outer surface of the developing roller and the occurrence of toner filming associated with long-term use. Patent Document 1 discloses a developing roller in which only the vicinity of the outer surface of the surface layer containing a crosslinked urethane resin is made to have high hardness, so that the occurrence of scratches on the outer surface and the occurrence of toner filming are suppressed at an extremely high level, and a process cartridge having the same is disclosed. Further, Patent Document 2 discloses a developing device in which silicone resin fine particles are applied to a developing roller. BACKGROUND ART DOCUMENTS PATENT DOCUMENTS
[0004] PATENT DOCUMENT 1 Japanese Patent Laid-Open No. 2020-166227 PATENT DOCUMENT 2 Japanese Patent Laid-Open No. 2017-062335 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0005] However, according to the inventors' research, when a developing device having a developing roller according to Patent Document 1 is left in a high-temperature, high-humidity environment for a long period of time, the following phenomenon may occur. Specifically, at the contact position between the toner supply roller and the developing roller, bleed material from the toner supply roller to the developing roller accumulates on the outer surface of the developing roller, causing band-like unevenness in the electrophotographic image at the pitch of the developing roller. Hereafter, an electrophotographic image with band-like unevenness may be referred to as a "band image". Furthermore, preventing the occurrence of band images was difficult even when a coating agent consisting of silicone resin fine particles was pre-applied to the developing roller, as described in Patent Document 2.
[0006] At least one aspect of this disclosure relates to a developing apparatus that can prevent the formation of band images even after being left in a high-temperature, high-humidity environment. At least one aspect of this disclosure relates to a method for cleaning a developing roller that can better remove deposits from the outer surface of the developing roller. [Means for solving the problem]
[0007] One aspect of the present disclosure is a developing apparatus comprising a developing roller, toner, and a toner supply roller for supplying the toner to the developing roller, The developing roller is A conductive substrate, A single surface layer on the substrate, It has, The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2): E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The adhesion rate of the silica particles to the toner particles, as measured by the water washing method, is 50% or more. Regarding developing equipment.
[0008] Another aspect of this disclosure is a cleaning method for cleaning the outer surface of a developing roller on which a plurality of fine particles are attached to the outer surface, The developing roller has a conductive substrate and a single-layer surface layer on the substrate. The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2), E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The cleaning method is The process includes supplying toner to the developing roller using a toner supply roller, and bringing into contact with a plurality of fine particles adhering to the outer surface of the surface layer the toner to remove the fine particles from the outer surface of the surface layer, The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The present invention relates to a cleaning method in which the adhesion rate of silica particles to toner particles, as measured by a water washing method, is 50% or more.
[0009] Furthermore, according to yet another aspect of this disclosure, an electrophotographic image forming apparatus having the developing apparatus is provided. An electrophotographic image forming apparatus is provided, which includes an electrophotographic process cartridge that is detachably configured to be attached to the main body of the apparatus, and the developing device. [Effects of the Invention]
[0010] According to this disclosure, even with a developing roller that can suppress the occurrence of scratches and filming to an extremely high degree, a developing apparatus can be obtained that can suppress the occurrence of band images of the developing roller pitch when left in a high-temperature, high-humidity environment, thereby enabling the production of highly durable and high-quality images. Furthermore, according to this disclosure, a method for cleaning the outer surface of the developing roller is provided. In addition, according to other aspects of this disclosure, a process cartridge and an electrophotographic image forming apparatus capable of stably outputting high-quality electrophotographic images is provided. [Brief explanation of the drawing]
[0011] [Figure 1] Cross-sectional view of the developing device, and enlarged view of the contact position between the developing roller and the toner supply roller. [Figure 2]A schematic cross-sectional view of the developing roller, and an enlarged view including its surface layer and outer surface. [Figure 3] Magnified schematic diagram of toner being pressed onto the surface layer of the developing roller. [Figure 4] A diagram showing an example of a substantially hemispherical shape in a microparticle. [Figure 5] (a)-(c) Figures showing examples of the maximum length df, maximum height h, and maximum width b when observing a microparticle in cross-section; (d)-(g) Figures showing examples of the major axis l1 of ellipse e1, the major axis l2 of ellipse e2, the minor axis s1 of ellipse e1, and the minor axis s2 of ellipse e2 when observing a microparticle in cross-section. [Figure 6] Cross-section of a process cartridge [Figure 7] Cross-sectional view of an electrophotographic image forming apparatus [Figure 8] A diagram illustrating the longest diameter w when observing a microparticle from any one direction. [Figure 9] Schematic diagram of EDS line analysis in STEM-EDS mapping analysis [Modes for carrying out the invention]
[0012] In this disclosure, descriptions of numerical ranges such as "XX or greater and YY or less" or "XX to YY" mean a numerical range that includes the lower and upper limits, unless otherwise specified. When numerical ranges are described in steps, the upper and lower limits of each numerical range can be combined in any way.
[0013] The present inventors speculate as follows why, when using a developing apparatus having a developing roller as described in Patent Document 1, if the developing apparatus is left in a high-temperature, high-humidity environment for a long period of time, band images of the developing roller pitch (band images generated at the circumferential interval of the developing roller) may appear in the image.
[0014] After a developing unit is manufactured with components such as developing rollers and toner supply rollers assembled, it may be left in a high-temperature, high-humidity environment for extended periods during transportation and storage, remaining in its manufactured state. During this time, at the contact point between the toner supply roller and the developing roller, bleed material from the toner supply roller—that is, unreacted resin residue or ionic conductive agent components added to impart conductivity—may transfer from the toner supply roller to the developing roller.
[0015] In the case of conventional developing rollers with a flexible surface layer, that is, developing rollers that do not have high hardness only near the outer surface of the surface layer as in Patent Document 1, even if the bleed material transfers to the developing roller, it is thought that it penetrates into the interior through the gaps in the cross-linking structure of the flexible surface layer, making it difficult for the bleed material to remain on the outer surface of the developing roller. Therefore, the concentration of the bleed material is unlikely to become locally high on the outer surface of the developing roller that is in direct contact with the toner. As a result, it is thought that band images are less likely to be formed.
[0016] On the other hand, in the case of a developing roller in which the vicinity of the outer surface of the surface layer is hardened, according to Patent Document 1, As described above, the occurrence of scratches on the outer surface and the occurrence of toner filming can be suppressed. However, because the crosslinking density near the outer surface of the surface layer is high, bleed material from the toner supply roller does not easily penetrate into the interior of the surface layer. Therefore, it is thought that the bleed material tends to be locally concentrated at the contact point with the toner supply roller on the outer surface of the developing roller. As a result, it is thought that the electrostatic charge on the toner and the adhesion of toner components at this contact point of the developing roller are significantly different compared to other positions, making it easier for a band of the developing roller pitch to appear in the electrophotographic image.
[0017] The occurrence of band images caused by the localized adhesion of bleed material to the surface of the developing roller, as described above, cannot be sufficiently prevented even if a coating agent such as silicone resin particles is present between the developing roller and the component, as in the developing container described in Patent Document 2. This is thought to be because, even if a coating agent is simply present between the toner supply roller and the developing roller, bleed material can travel along the outer surface or inside of the coating agent and reach the outer surface of the developing roller.
[0018] Therefore, the inventors conducted extensive research to obtain a developing apparatus that can prevent the formation of band images even after being left in a high-temperature, high-humidity environment, based on the premise of using a developing roller with excellent scratch resistance to the outer surface, where only the vicinity of the outer surface of the surface layer has high hardness. As a result, they found that by having fine particles with a specific shape on the outer surface of the developing roller in a specific manner, it is possible to prevent localized adhesion of bleed material to the outer surface of the toner supply roller. In other words, by having the bleed material mainly adhere to the fine particles attached to the outer surface of the developing roller, it is possible to prevent localized adhesion of bleed material to the outer surface of the toner supply roller.
[0019] In other words, one aspect of the present disclosure is a developing apparatus comprising a developing roller, toner, and a toner supply roller for supplying the toner to the developing roller, The developing roller is A conductive substrate, A single surface layer on the substrate, It has, The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2): E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The adhesion rate of the silica particles to the toner particles, as measured by the water washing method, is 50% or more. Regarding developing equipment.
[0020] Furthermore, when forming high-quality electrophotographic images after storage in a high-temperature, high-humidity environment in a developing device, Therefore, it is preferable to promptly remove any bleed particles adhering to the outer surface of the developing roller. Accordingly, the inventors have also investigated methods for cleaning the developing roller by removing specific particles with a specific shape that have been adhered to its outer surface in a specific manner. As a result, they found that the above objective can be effectively achieved by using a specific toner in the developing apparatus.
[0021] In other words, one aspect of the present disclosure is a cleaning method for cleaning the outer surface of a developing roller on which a plurality of fine particles are attached to the outer surface, The developing roller has a conductive substrate and a single-layer surface layer on the substrate. The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2), E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The cleaning method is The process includes supplying toner to the developing roller using a toner supply roller, and bringing into contact with a plurality of fine particles adhering to the outer surface of the surface layer the toner to remove the fine particles from the outer surface of the surface layer, The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The present invention relates to a cleaning method in which the adhesion rate of silica particles to toner particles, as measured by a water washing method, is 50% or more.
[0022] Here, Figure 1 shows a cross-sectional view of a developing apparatus according to one embodiment of the present disclosure, and an enlarged view of the contact position between the developing roller and the toner supply roller. The developing apparatus 1 shown in Figure 1 includes a developing roller 2, a toner supply roller 3, a developing container 6 that houses a developing blade 5, and a toner container 8 that houses toner 7. The developing roller 2 is assembled to contact the toner supply roller 3 and the developing blade 5. The toner supply roller 3 supplies toner 7 to the developing roller 2.
[0023] In the developing device 1 before initial use, the toner 7 may be present inside the developing container 6 or at the contact position between the developing roller 2 and the toner supply roller 3, to the extent that it does not hinder the effects of the present invention. As shown in Figure 1, it is preferable that the toner 7 is separated from the developing container 6 by a sealing member 9 or the like. In the developing device 1 in which the toner 7 is separated from the developing container 6 by a sealing member 9, the sealing member 9 is removed before the development device 1 is put into use, so that the toner 7 flows into the inside of the developing container 6 through an opening provided in the toner container 8.
[0024] Furthermore, the developing roller 2 provided in a developing apparatus 1 according to one aspect of this disclosure has a conductive substrate and a single-layer surface layer on the substrate. In the developing roller 2, a plurality of fine particles 4 are attached to the outer surface of the surface layer. The fine particles form protrusions on the outer surface of the surface layer. In a cross-sectional view of the fine particles 4 and the outer surface, each of the fine particles 4 is in surface contact with the outer surface of the surface layer. It has a flat surface 10 and a curved surface 11 that constitutes at least a part of the convex portion (preferably constituting the convex portion). For example, the fine particles 4 have a substantially hemispherical shape having a substantially flat surface and a curved surface. The substantially flat surface 10 is in contact with the outer surface of the developing roller 2, and each of the fine particles 4 has a curved surface 11 that is convex in the direction opposite to the substantially flat surface 10.
[0025] In other words, the nearly flat surface of the fine particles 4 and the outer surface of the developing roller 2 come into contact over a surface area, increasing the contact area. As the contact area between the fine particles 4 and the developing roller 2 increases, bleed material from the toner supply roller 3 adheres to and accumulates on the outer surface of the fine particles 4, while direct adhesion and accumulation on the outer surface of the developing roller 2 can be significantly suppressed.
[0026] Furthermore, the inventors have found that the band image can be quickly suppressed by enabling the rapid removal of fine particles 4 from the outer surface of the developing roller 2 when the developing device 1 is driven. The developing device 1, which is equipped with a developing roller 2 on which fine particles 4 have adhered to the outer surface and a toner supply roller 3 in contact, is left in a high-temperature, high-humidity environment for a long period of time. In this case, as described above, the bleed material adheres to and accumulates on the outer surface of the fine particles 4 that are present at the contact position between the developing roller 2 and the toner supply roller 3.
[0027] If the developing device 1 is driven after being left unattended, and the fine particles 4 remain on the outer surface of the developing roller 2, then there will be areas on the outer surface of the developing roller 2 where fine particles 4 with bleed material attached and accumulated exist, and areas where fine particles 4 without bleed material exist. Since the electrostatic charge on the toner and the adhesion of toner components differ greatly between these areas, a band image will ultimately occur. However, according to one embodiment of the developing apparatus 1 of this disclosure, the fine particles 4 are quickly removed from the outer surface of the developing roller 2 when the developing apparatus 1 is driven, and the bleed material along with the fine particles 4 is removed from the outer surface of the developing roller 2. Furthermore, as described above, direct adhesion and accumulation of bleed material is suppressed on the outer surface of the developing roller 2 by the fine particles 4, so it is considered that the band image can be quickly suppressed in the end.
[0028] The conditions under which the fine particles 4 can be quickly removed from the outer surface of the developing roller 2 are described below. The first is the condition of the developing roller. Figure 2 is a cross-sectional view perpendicular to the longitudinal direction of a developing roller 2 having a conductive substrate consisting of a core body 21 and an intermediate layer 22, and a single-layer surface layer 23, as well as an enlarged view including the surface layer 23 and its outer surface 24.
[0029] The surface layer 23 of the developing roller 2 is a single layer and has a matrix containing crosslinked urethane resin as a binder. As shown in the enlarged view of Figure 2, the region from the outer surface 24 of the surface layer 23 to a depth of 0.1 μm is the first region 25, and the region from a depth of 1.0 μm to 1.1 μm is the second region 26. When the elastic modulus of the matrix in the first region 25 is E1, and the elastic modulus of the matrix in the second region 26 from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, The following equations (1) and (2) are satisfied simultaneously. E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2)
[0030] As described above, the nearly flat surface of the fine particles comes into contact with the developing roller over a surface area, and as this contact area increases, bleed material from the toner supply roller adheres to and accumulates on the outer surface of the fine particles. Therefore, direct adhesion and accumulation of bleed material on the outer surface of the developing roller can be significantly suppressed. On the other hand, the adhesion force between the fine particles and the surface of the developing roller increases in proportion to the increase in contact area, making it difficult to remove the fine particles with bleed material attached and accumulated from the outer surface of the developing roller. However, by setting the elastic modulus E1 of the matrix in the first region, which is near the outer surface of the developing roller surface layer, to a high hardness of 200 MPa or more, the tackiness between the fine particles and the outer surface of the developing roller is reduced, and the adhesion force can be significantly reduced. As a result, even when the contact area between the fine particles and the outer surface of the developing roller is large, it becomes possible to remove the fine particles from the outer surface of the developing roller by rubbing and polishing with a specific toner described later.
[0031] In addition, by limiting the high-hardness region to the vicinity of the outer surface of the developing roller surface layer and making the interior of the surface layer flexible, that is, by setting the elastic modulus E2 of the matrix in the second region above to 10 MPa or more and 100 MPa or less, it becomes possible to quickly remove fine particles.
[0032] Here, Figures 3(a) and 3(b) show enlarged schematic diagrams of when the toner 7 is pressed against the developing roller surface layer 23 by the contact member 31. When the developing apparatus according to this disclosure is driven, the toner 7 receives contact pressure 32 from the contact member 31, such as the developing blade or toner supply roller, and is pressed against and rubbed against the developing roller surface layer 23. As a result, the outer surface of the developing roller surface layer 23 is polished by the toner 7, and fine particles 4 adhering to the outer surface are removed.
[0033] As shown in Figure 3(a), if the entire surface layer 23 of the developing roller is a high-hardness region 33, the surface layer 23 does not deform even when pressed by the toner 7. Therefore, the contact area with the toner 7, which acts as an abrasive, is small, i.e., the area that a single toner particle can abrasive, and the fine particles 4 cannot be removed quickly.
[0034] On the other hand, if the high-hardness region 33 is limited to an extremely thin first region near the outer surface, as in the developing roller of this disclosure, and the interior (second region) is flexible, the surface layer 23 can deform along the shape of the toner 7 due to the pressure from the toner 7. This increases the contact area between the toner 7 and the developing roller surface layer 23 when pressed, allowing a single toner particle to polish a wide area of the outer surface of the developing roller. In this case, since the area near the outer surface of the developing roller is highly hard as described above, and the adhesion force between the fine particles 4 and the developing roller is reduced, the fine particles can be quickly removed from the outer surface of the surface layer of the developing roller by polishing with the toner 7.
[0035] By setting the elastic modulus E2 of the matrix in the second region described above to 100 MPa or less, as described above, when the toner is pressed against the surface layer of the developing roller by the contact member, the surface layer of the developing roller can deform to follow the shape of the toner. This increases the contact area between the pressed toner and the outer surface of the developing roller, allowing a single toner particle to polish a wide area of the outer surface of the developing roller. Furthermore, having an elastic modulus E2 of 10 MPa or higher provides the flexibility necessary to apply sufficient reaction force to the toner for polishing during friction associated with the operation of the developing device. Thus, even if the outer surface of the developing roller's surface layer is highly hard, this hardness is limited to only a very thin area of the outer surface, and the interior remains sufficiently flexible, allowing fine particles to be quickly removed from the outer surface of the surface layer.
[0036] The second condition concerns the fine particles. Each fine particle is substantially hemispherical in shape, having both a substantially flat surface and a curved surface, and contains an organosilicon compound. Furthermore, in a cross-sectional view of the fine particles and the outer surface when the fine particles are in contact with the outer surface of the developing roller, the substantially flat surface of each fine particle is in contact with the outer surface of the developing roller, and each fine particle has a curved surface that is convex in the direction opposite to the substantially flat surface. In addition, the number-average value of the longest diameter w of the substantially flat surface of the fine particles is 10 to 400 nm.
[0037] The fine particles form protrusions on the surface of the surface layer. In a cross-sectional view of the fine particles and the outer surface, each fine particle has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. That is, as shown in the enlarged view of Figure 1, the fine particles have a substantially flat surface. The particles are attached to the outer surface of the developing roller so that they are in contact with the outer surface of the developing roller. This allows the curved surface of the fine particles to interlock with the silica particles acting as an external additive toner during friction caused by the development device's operation, enabling the fine particles to receive the necessary shear force to be removed from the surface of the developing roller.
[0038] Furthermore, the inclusion of organosilicon compounds in the fine particles allows for affinity with both the resin outer surface of the developing roller and the silica particles, which are silicon compounds. In addition to the shape of the fine particles, this affinity makes it easier to maintain a large contact area between the fine particles and the outer surface of the developing roller, thereby suppressing the adhesion and accumulation of the aforementioned bleed material on the outer surface of the developing roller. Moreover, when the fine particles interlock with the silica particles, the affinity between the silica particles and the fine particles facilitates appropriate chemical adhesion, making it easier for the fine particles to receive the shear force necessary to remove them from the outer surface of the developing roller.
[0039] Furthermore, when the average number of the longest diameter w of the nearly planar surface of the fine particles is 10 nm or more, the fine particles containing organosilicon compounds and the silica particles used as an external additive interlock easily, allowing the fine particles to be quickly removed from the outer surface of the developing roller. In addition, when the average number of w is 400 nm or less, the contact area between the nearly planar surface of the fine particles and the outer surface of the developing roller tends to be large, which suppresses the adhesion and accumulation of bleed material on the outer surface of the developing roller.
[0040] The third requirement concerns the toner. The toner consists of toner particles and silica particles as an external additive. The toner particles contain a binder resin. Furthermore, the adhesion rate of the silica particles to the toner particles, as measured by the water washing method, must be 50% or higher.
[0041] As described above, the presence of silica particles as an external additive in the toner allows it to interlock with fine particles containing organosilicon compounds during the operation of the developing device, making it easier to apply the shear force necessary to remove the fine particles from the outer surface of the developing roller. In addition, since silica particles are inorganic silicon compounds and have high hardness compared to resin, they can exhibit sufficient polishing properties against developing rollers with high hardness near the outer surface and fine particles containing organosilicon compounds. Furthermore, because the toner particles contain a binder resin and the adhesion rate of silica particles is 50% or more, the adhesion force between the silica particles and the toner particles exceeds the adhesion force between the fine particles and the developing roller. Therefore, the shear force when the toner particles interlock with the fine particles can remove them from the outer surface of the developing roller.
[0042] As described above, the three conditions do not work independently, but rather, when all are satisfied simultaneously, a series of effects occur: the suppression of the adhesion and accumulation of bleed material by fine particles on the outer surface of the developing roller, and the rapid removal of fine particles by toner, leading to the rapid suppression of band images. The aspects of this disclosure are described below.
[0043] <developing roller> Figure 2 shows a cross-sectional view perpendicular to the longitudinal direction of a developing roller 2 having a conductive substrate consisting of a core body 21 and an intermediate layer 22, and a single-layer surface layer 23, as well as an enlarged view of the surface layer 23. The intermediate layer 23 may be a single layer or multiple layers. For example, in a non-magnetic one-component contact developing system process, a developing roller in which the surface layer 23 is provided on a conductive substrate consisting of an intermediate layer 22 laminated on a core body 21 is preferably used.
[0044] 1. Conductive substrate The conductive substrate can be a cylindrical or hollow cylindrical conductive core body 21, and one or more conductive intermediate layers 22 provided on such a core body. The shape of the core body 21 is cylindrical or hollow cylindrical and is made of one of the following conductive materials: metal or alloy such as aluminum, copper alloy, or stainless steel; iron plated with chromium or nickel; conductive synthetic resin. The surface of the core body 21 has an intermediate layer on its outer circumference. A known adhesive can also be applied to improve adhesion to 22 and the surface layer 23, etc.
[0045] As described above, in the non-magnetic one-component contact developing system process, a developing roller in which an intermediate layer 22 is laminated between the shaft core 21 and the surface layer 23 is preferably used. The intermediate layer 22 provides the developing roller 2 with hardness and elasticity such that it is pressed against the photoreceptor with an appropriate nip width and nip pressure, so that toner can be supplied without excess or deficiency to the electrostatic latent image formed on the surface of the photoreceptor.
[0046] The intermediate layer 22 is preferably formed from a molded rubber material. Examples of rubber materials include: ethylene-propylene-diene copolymer rubber (EPDM), acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), natural rubber (NR), isoprene rubber (IR), styrene-butadiene rubber (SBR), fluororubber, silicone rubber, epichlorohydrin rubber, hydrogenated NBR, and urethane rubber. These can be used individually or in combination of two or more types. Among these, silicone rubber is particularly preferred because it is less likely to cause compression set even when in contact with other components (such as toner control members) over a long period of time. Specifically, examples of silicone rubber include cured products of addition-curing type silicone rubber.
[0047] The thickness of the intermediate layer 22 is preferably 0.5 mm or more and 10 mm or less. A thickness of 0.5 mm or more and 10 mm or less for the intermediate layer 22 is preferable because it makes it easier to achieve an appropriate nip width and nip pressure. More preferably, it is 1 mm or more and 5 mm or less.
[0048] Furthermore, the intermediate layer 22 can be an intermediate layer 22 in which a conductivity imparting agent such as an electronically conductive substance or an ionic conductive substance is blended with the above rubber material. The volume resistivity of the intermediate layer 22 is preferably 10 3 Ω cm or more 10 11 Ω·cm or less, more preferably 10 4 Ω cm or more 10 10 It will be adjusted to Ω·cm or less.
[0049] 2.Surface layer The surface layer 23 is a single layer and has a matrix containing a crosslinked urethane resin as a binder. As shown in the enlarged view of Figure 2, the region from the outer surface 24 of the surface layer 23 to a depth of 0.1 μm is the first region 25, and the region from a depth of 1.0 μm to 1.1 μm is the second region 26. The elastic modulus of the matrix in the first region 25 is denoted as E1, and the elastic modulus of the matrix in the second region 26 from the outer surface to a depth of 1.0 μm to 1.1 μm is denoted as E2. At this time, equations (1) and (2) below are simultaneously satisfied. E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2)
[0050] In other words, the surface layer 23 has a highly hardened extremely thin region near the outer surface 24, while the region inside that region remains flexible.
[0051] The elastic modulus E1 of the first region is 200 MPa (200 × 10⁻¹⁰ MPa). 6 The pressure is 200 MPa or higher. By setting E1 to 200 MPa or higher, the tackiness between the fine particles and the outer surface of the developing roller is reduced, as described above, and the adhesion force can be significantly suppressed. As a result, even when the contact area between the fine particles and the outer surface of the developing roller is large, the fine particles can be removed from the outer surface of the developing roller by rubbing and polishing with a specific toner. There is no particular upper limit to the elastic modulus E1 of the first region, but it is set within an appropriate range in relation to the elastic modulus E2 of the second region. Typically, the elastic modulus E1 of the first region is 4500 MPa (4500 × 10⁻¹⁰ MPa). 6 It is preferable that it is less than or equal to Pa. The modulus of elasticity E1 is preferably 200 to 4500 MPa, and more preferably 200 to 1 The pressure is 200 MPa, more preferably 350 to 1050 MPa, and even more preferably 450 to 1020 MPa.
[0052] Furthermore, the elastic modulus E2 of the second region is 10 to 100 MPa. By setting E2 to 10 to 100 MPa, fine particles can be removed quickly as described above. Preferably, it is 15 to 50 MPa, more preferably 20 to 50 MPa, and even more preferably 20 to 30 MPa. The elastic moduli E1 and E2 can be measured using a scanning probe microscope (SPM), as described later.
[0053] This high hardening, limited to the vicinity of the outer surface, can be achieved by impregnating and crosslinking acrylic monomers into a crosslinked urethane resin. In particular, by including crosslinked urethane resin as a binder in the matrix, even when the elastic modulus of the impregnated and crosslinked acrylic monomers (crosslinked acrylic resin) is extremely high, the toughness of the crosslinked urethane resin can suppress the embrittlement of the crosslinked acrylic. As a result, as described above, even if the surface layer of the developing roller deforms to follow the shape of the toner when the toner is pressed against it, cracks and scratches are less likely to occur, thus enabling high durability as a developing roller.
[0054] Furthermore, by including a cross-linked urethane resin as a binder in the matrix, it is possible to form an interpenetrating polymer network structure (hereinafter referred to as IPN structure) together with the cross-linked acrylic resin.
[0055] An IPN structure is a network structure in which two or more polymer molecules are intertwined and entangled without being bound together by covalent bonds. This structure will not unravel unless the molecular chains forming the network are cleaved. Several methods can be used to form an IPN structure. For example, a sequential network formation method is used, in which a network of the first component polymer is formed first, and then the second component monomer and polymerization initiator are used to swell the polymer, after which a network of the second component polymer is formed. Alternatively, a simultaneous network formation method is used, in which the first component monomer, the second component monomer, and their respective polymerization initiators, which have different reaction mechanisms, are mixed together to form a network simultaneously.
[0056] Furthermore, resin particles may be added to the surface layer for the purpose of forming protrusions on the outer surface of the developing roller. If the surface layer is to have surface roughness, fine particles for imparting roughness to the surface layer may be included. Specifically, fine particles of polyurethane resin, polyester resin, polyether resin, polyamide resin, acrylic resin, and polycarbonate resin can be used. These are also preferably crosslinked resin particles. Crosslinked urethane beads are a preferred example. Furthermore, the thickness of the surface layer is preferably 4 μm to 100 μm. The layer thickness is the thickness in the portion where the previously formed protrusions are not formed. A layer thickness of 4 μm to 100 μm is preferable because it facilitates flexible deformation of the surface layer. More preferably, it is 6 μm to 30 μm, and even more preferably, 10 μm to 25 μm.
[0057] 2-1. Cross-linked urethane resin The matrix contains a crosslinked urethane resin as a binder. The crosslinked urethane resin included in the matrix is not particularly limited, as long as it can achieve the elastic modulus E2 described above. Polyurethane can be obtained from polyols, isocyanates, and, if necessary, chain extenders. Polyols used as raw materials for polyurethane include polyether polyols, polyester polyols, polycarbonate polyols, polyolefin polyols, and acrylic polyols. Examples include ol, and mixtures thereof.
[0058] Examples of isocyanates used as raw materials for polyurethanes include: tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymeric MDI, naphthalene diisocyanate (NDI), tolidine diisocyanate (TODI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), tetramethyl xylylene diisocyanate (TMXDI), cyclohexane diisocyanate, and mixtures thereof.
[0059] Among the above, polymeric MDI is preferred. Here, polymeric MDI is represented by the following chemical formulas (1) and (1)'. In chemical formula (1)', n is preferably between 1 and 4. Chemical formula (1) is the case where n is 1 in chemical formula (1)'. Polymeric MDI can be commercially available, such as the Millionate MR series (manufactured by Tosoh Corporation), including the Millionate MR200 (product name). [ka]
[0060] Chain extenders used as raw materials for polyurethanes include ethylene glycol, bifunctional low molecular weight diols such as 1,4-butanediol and 3-methylpentanediol, trifunctional low molecular weight triols such as trimethylolpropane, and mixtures thereof. Furthermore, prepolymer-type isocyanate compounds having isocyanate groups at their terminal ends may be used, which are obtained by pre-reacting the above-mentioned isocyanate compounds with various polyols in an excess of isocyanate groups. In addition, as these isocyanate compounds, materials in which the isocyanate groups have been blocked with various blocking agents such as MEK oxime may be used.
[0061] The elastic modulus E2 can be adjusted to the above range by the molecular structure of the crosslinked urethane resin and the interaction caused by the addition of fine particles such as silica and carbon black. Specifically, for example, E2 can be increased by reducing the molecular weight of the polyol or isocyanate, increasing the number of hydroxyl groups or isocyanate groups, and increasing the amount of fine particles added. Conversely, E2 can be decreased by increasing the molecular weight of the polyol or isocyanate, decreasing the number of hydroxyl groups or isocyanate groups, and decreasing the amount of fine particles added.
[0062] 2-2. Cross-linked acrylic resin The surface layer preferably has a cross-linked acrylic resin impregnated with a cross-linked urethane resin. The type of acrylic monomer to be impregnated into the crosslinked urethane resin and crosslinked is preferably a polyfunctional monomer having multiple (two or more) acryloyl groups or methacryloyl groups as functional groups in order to form a crosslinked structure. Here, it is preferable that the number of functional groups be 6 or less, as this suppresses the increase in viscosity of the acrylic monomer and allows the acrylic monomer to easily penetrate into the interior without remaining on the outer surface of the surface layer. Furthermore, it is even more preferable to use an acrylic monomer with 4 or fewer functional groups, as when used in combination with a surfactant, the acrylic monomer does not easily remain on the outer surface of the surface layer and penetrates into the interior, and also tends to remain in the vicinity of the outer surface of the surface layer, for example, in a region with a depth of less than 1 μm. Di(meth)acrylates such as neopentyl glycol diacrylate and PO (propylene oxide) modified neopentyl glycol diacrylate are preferred.
[0063] The molecular weight of the acrylic monomer is preferably in the range of 200 to 750. By using a molecular weight in this range, the acrylic monomer can be efficiently impregnated into the binder resin contained in the surface layer, and the hardness of the area near the outer surface can be increased. In other words, by selecting one or more acrylic monomers that satisfy the above-mentioned molecular weight range and viscosity range, impregnating the surface layer with them, and crosslinking them, the hardness of the area near the outer surface of the surface layer can be increased.
[0064] The method for crosslinking the acrylic monomer is not particularly limited, and known methods can be used. Specifically, methods such as heating and ultraviolet irradiation can be used. For each polymerization method, known radical polymerization initiators or ionic polymerization initiators can be used.
[0065] Examples of polymerization initiators when polymerization is carried out by heating include peroxides such as 3-hydroxy-1,1-dimethylbutyl peroxyneodecanoate, α-cumyl peroxyneodecanoate, t-butyl peroxyneoheptanoate, t-butyl peroxybivalate, t-amyl peroxyn-octoate, t-butyl peroxy 2-ethylhexyl carbonate, dicumyl peroxide, di-t-butyl peroxide, di-t-amyl peroxide, 1,1-di(t-butylperoxy)cyclohexane, and n-butyl-4,4-di(t-butylperoxy)valerate; Examples of azo compounds include 2,2-azobisbutyronitrile, 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylbutyronitrile), 1,1-azobis(cyclohexane-1-carbonnitrile), 2,2-azobis[2-(2-imidazolin-2-yl)propane], 2,2-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2-azobis(N-butyl-2-methoxypropionamide), and dimethyl-2,2-azobis(isobutyrate).
[0066] Examples of polymerization initiators when polymerization is performed by UV irradiation include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)- Benzyl]-phenyl}-2-methylpropan-1-one, 2-methyl-1-[4-(methylpropan-1-one) [Tylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxy Another example is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0067] These polymerization initiators may be used individually or in combination of two or more types. Furthermore, the amount of polymerization initiator used is preferably 0.5 parts by mass or more and 10 parts by mass or less, from the viewpoint of efficiently carrying out the reaction, when the total amount of the compound for forming the specific resin (for example, a compound having a (meth)acryloyl group) is 100 parts by mass.
[0068] Furthermore, known heating devices and ultraviolet irradiation devices can be used as appropriate. As light sources for ultraviolet irradiation, for example, LED lamps, high-pressure mercury lamps, metal halide lamps, xenon lamps, and low-pressure mercury lamps can be used. The cumulative light amount required during polymerization can be adjusted as appropriate depending on the type and amount of the compound and polymerization initiator used.
[0069] Methods to confirm the presence of cross-linked acrylic resin in a matrix containing cross-linked urethane resin include, for example, the following: (1) confirmation by solvent extraction, (2) confirmation of changes in the glass transition temperature before and after impregnation treatment, (3) confirmation of changes in the peak top temperature of the thermal chromatogram before and after impregnation treatment, and (4) confirmation by μMS.
[0070] 2-3. Conductive Agent A conductive agent can be incorporated into the surface layer to control its conductivity. Examples of conductive agents incorporated into the surface layer include ionic conductive agents and electronic conductive agents such as carbon black. Among these, carbon black is preferred because it can control both the conductivity of the conductive elastic layer and its charging performance with respect to the toner. The volume resistivity of the conductive elastic layer is 1 × 10⁻⁶. 3 Ω cm or more 1×10 11 It is preferable that the range is Ω·cm or less.
[0071] 2-4. Additives The surface layer may contain various additives, to the extent that they do not impair the features of the present disclosure. In particular, it is preferable that the surface layer (e.g., matrix) further contains at least one surfactant selected from the group consisting of silicone-based surfactants and fluorine-based surfactants, and more preferably contains a silicone-based surfactant. Surfactants can possess both low-polarity groups, such as silicone-containing or fluorine-containing groups, and high-polarity groups in their modification sites. Due to the large polarity difference between the urethane groups or other high-polarity groups of the cross-linked urethane resin and the low-polarity groups, such as silicone-containing or fluorine-containing groups, in the surfactant molecule, the surfactant migrates and remains near the outer surface of the surface layer. Furthermore, when acrylic monomers are impregnated into this surfactant-containing matrix, the acrylic monomers tend to remain near the surfactant. In particular, impregnating with acrylic monomers that have a similar polarity to the highly polar groups of the surfactant is preferable, as they tend to remain near the outer surface. Subsequently, by crosslinking the impregnated acrylic monomers, the matrix present in the region near the outer surface of the surface layer can be locally hardened.
[0072] Furthermore, if the surfactant is a silicone-based surfactant, it is even more preferable because it has even better affinity with fine particles containing organosilicon compounds. The elastic modulus E1 can be adjusted to the above range by the molecular structure and state of existence of the impregnated and cured crosslinked acrylic resin, as well as its interaction with the crosslinked urethane resin. Specifically, E1 can be easily increased by reducing the molecular weight of the impregnated acrylic monomer or by increasing the amount of acryloyl or methacryloyl groups. Conversely, E1 can be easily decreased by increasing the molecular weight of the impregnated acrylic monomer or by decreasing the amount of acryloyl or methacryloyl groups.
[0073] 2-5. Method for forming the surface layer The method for forming the surface layer is not particularly limited, but it can be formed by, for example, the following method. A coating solution for forming a surface layer is prepared, containing, as necessary, a conductive agent, additives, resin particles, and a solvent, in addition to the composition that will serve as the raw material for the crosslinked urethane resin. A conductive substrate is dipped into the coating solution and dried to form a layer containing the crosslinked urethane resin as a binder on the conductive substrate.
[0074] Next, acrylic monomers and polymerization initiators are impregnated into the surface layer, and the acrylic monomers are crosslinked. A coating solution containing acrylic monomers, and optionally polymerization initiators, sensitizers, and solvents is prepared. Then, the coating solution is applied to a roller on which a layer containing crosslinked urethane resin has been formed, using a known coating method such as dipping, roll coating, or spray coating. This impregnates the layer containing the crosslinked urethane resin with acrylic monomers, etc. Next, after drying the solvent as necessary, the acrylic monomers are crosslinked by heating or ultraviolet irradiation to form the surface layer.
[0075] <Fine particles> Multiple microparticles are attached to the outer surface of the surface layer of the developing roller. The microparticles form protrusions on the outer surface of the surface layer. Each microparticle also contains an organosilicon compound. In a cross-sectional view of the microparticles and the outer surface, each microparticle has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially flat surface of the microparticles is 10 to 400 nm.
[0076] 1. Shape of fine particles In one aspect of this disclosure, the fine particles have substantially flat and curved surfaces, and for example, have a substantially hemispherical shape. In a cross-sectional view of the microparticles and the outer surface when the microparticles are in contact with the outer surface of the developing roller, the substantially flat surface of each microparticle is in surface contact with the outer surface of the surface layer. Furthermore, each microparticle has a curved surface that is convex in the direction opposite to the substantially flat surface. As a result, the substantially flat surface of the microparticles is in contact with the outer surface of the developing roller. In other words, the fine particles and the outer surface of the developing roller come into contact over a larger surface area. As a result of this increased contact area between the fine particles and the developing roller, bleed material from the toner supply roller adheres to and accumulates on the outer surface of the fine particles, while direct adhesion and accumulation on the outer surface of the developing roller is significantly suppressed.
[0077] Furthermore, because the fine particles have a curved surface that is convex in the direction opposite to the approximately flat plane, they can interlock with silica particles, which are an external additive for the toner, when rubbed by the drive of the developing device, and receive the shear force necessary to be removed from the surface of the developing roller.
[0078] A substantially hemispherical shape that a microparticle may have refers, for example, to the shape obtained by cutting an ellipsoid with an arbitrary plane. As shown in Figure 4, when an ellipsoid is divided into two parts with an arbitrary plane, one of the two solids (shown as a dot pattern in Figure 4) is an example of a substantially hemispherical shape in this disclosure. In this disclosure, the ellipsoid includes solids that approximate a perfect sphere or an ellipsoid, and any plane may or may not pass through the center of the ellipsoid.
[0079] Furthermore, the method for producing substantially hemispherical microparticles as described herein is not limited to the method of cutting an ellipsoid, but also includes methods such as forming them bottom-up on a substrate having a substantially flat surface. In the case of the bottom-up method on a substrate having a substantially flat surface, if particles having a substantially flat surface and a particle size several tens of times larger than the size of the microparticles are used as the substrate, the substrate will have both a substantially flat surface and a curved surface. This makes it easier to manufacture microparticles that are essentially hemispherical in shape.
[0080] The fact that a microparticle is substantially hemispherical can be confirmed by observing the cross-section that intersects the approximately flat plane of the microparticle. Specifically, when observing the cross-section of a microparticle, it is determined that the microparticle has a substantially hemispherical shape with both an approximately flat and a curved surface if the following two conditions (1) and (2) are met. Figures 5(a) to (c) illustrate this point.
[0081] (1) Observe the cross-section of the fine particles intersecting a nearly plane. In this cross-section, let Pa and Pb be the two intersection points of the line Lf originating from the nearly plane and the line Lc originating from the curved surface. Let the line connecting Pa and Pb be the virtual line Li, and let the maximum length df be the furthest distance between the virtual line Li and the line Lf originating from the nearly plane. In a cross-section, a line Ls1 intersects a virtual line Li perpendicularly. Let Pc be the intersection point of the virtual line Li and line Ls1, and let Pe be the intersection point of the line Lc originating from the curved surface and line Ls1. Let Da be the distance between intersection point Pc and intersection point Pe. Also, let Db be the distance between the intersection point Pd of the line Lf originating from a substantially plane and line Ls1, and the intersection point Pe of the line Lc originating from the curved surface and line Ls1. When the distance when either Da or Db is maximized is the maximum height h, the average value of the ratio df / h (the ratio of the maximum length df to the maximum height h) is between 0.00 and 0.10.
[0082] (2) Observe the cross-section where the fine particles intersect with a substantially flat plane. In this cross-section, let e1 be an ellipse that passes through two intersection points of the substantially flat plane and the curved surface (corresponding to Pa and Pb above) and is circumscribed on the curved surface of the fine particles. Also, let e2 be an ellipse that passes through two intersection points of the substantially flat plane and the curved surface and is inscribed on the curved surface of the fine particles. In e1 and e2, the average number of the ratio of the major axis l1 of ellipse e1 to the major axis l2 of ellipse e2, l1 / l2, is 0.90 to 1.10. Furthermore, the average number of the ratio of the minor axis s1 of ellipse e1 to the minor axis s2 of ellipse e2, s1 / s2, is 0.90 to 1.10.
[0083] Examples of maximum length df and maximum height h are shown in Figures 5(a) to (c). The average number of particles in the ratio df / h is preferably 0.00 to 0.05. Within this range, the contact area between the fine particles and the outer surface of the developing roller increases, suppressing the direct adhesion and accumulation of bleed material on the outer surface of the developing roller. Furthermore, examples of ellipses e1, e2, the major axis l1 of ellipse e1, the major axis l2 of ellipse e2, the minor axis s1 of ellipse e1, and the minor axis s2 of ellipse e2 are shown in Figures 5(d) to (g).
[0084] Furthermore, the average number of the longest diameter w of the fine particles on a nearly flat surface is between 10 and 400 nm. When the average number of the longest diameter w is 10 nm or more, the fine particles containing organosilicon compounds and the silica particles used as an external additive interlock easily, allowing the fine particles to be quickly removed from the outer surface of the developing roller. Furthermore, when the average number of the longest diameter w is 400 nm or less, the contact area between the nearly flat surface of the fine particles and the outer surface of the developing roller tends to be large, suppressing the adhesion and accumulation of bleed material on the outer surface of the developing roller. The average number of particles with the longest diameter w is preferably 30 to 250 nm, and more preferably 50 to 120 nm. When the average number of particles with the longest diameter w is 30 nm or more, the fine particles become more easily interlocked with the silica particles. Furthermore, when the average number of particles with the longest diameter w is 250 nm or less, the contact area between the nearly flat surface of the fine particles and the outer surface of the developing roller tends to be large, making it less likely for bleed material to directly adhere to and accumulate on the outer surface of the developing roller, which is preferable.
[0085] The average number of particles with the longest diameter w can be controlled by the type and amount of monomer used in the production of the fine particles, the reaction temperature and time during monomer polymerization, the reaction medium and the pH of the reaction system, and the type and concentration of the dispersant. Furthermore, when producing fine particles by a bottom-up method on a substrate, the shape and size of the substrate can also control the shape of the fine particles and the average number of particles with the longest diameter w. This is possible.
[0086] Furthermore, when observing a cross-section of a microparticle that intersects a substantially plane, two intersection points are defined as Pa and Pb, where Lf originates from the substantially plane and Lc originates from the curved surface. The line connecting the intersection points Pa and Pb is defined as a virtual line Li. In a line Ls1 that intersects the virtual line Li perpendicularly, the intersection point between the virtual line Li and line Ls1 is defined as Pc, and the intersection point between line Lc and line Ls1 is defined as Pe. The distance between intersection point Pc and intersection point Pe is defined as Da. Also, the distance between the intersection point Pd of line Lf and line Ls1 and the intersection point Pe is defined as Db. The maximum height h is defined as the distance when either Da or Db is maximized. On the other hand, in a line Ls2 parallel to the virtual line Li (Ls2 may be the same as Li), let Pf and Pg be the two intersection points where line Ls2 and line Lc intersect, and let the maximum width b be the distance at which the distance Dc between Pf and Pg is maximized. In this case, it is preferable that the average value of the ratio h / b, which is the ratio of the maximum height h to the maximum width b, is 0.30 to 0.80. More preferably, it is 0.40 to 0.70, and even more preferably, 0.50 to 0.60.
[0087] The ratio h / b is calculated by measuring h and b in a single microparticle when observing the cross-section of the microparticle. Examples of h and b are shown in Figures 5(a) to (c).
[0088] When the average number of h / b particles is 0.30 or higher, the convexity in the direction opposite to the approximately plane in contact with the developing roller increases, making it easier for the particles to interlock with the silica particles used as an external additive for the toner. Conversely, when the average number of h / b particles is 0.80 or lower, the convexity does not become too high, making it easier to maintain a high contact area of the fine particles with the outer surface of the developing roller, even when subjected to vibrations that occur during assembly of the developing device at the contact point between the developing roller and the toner supply roller.
[0089] The average number of particles in the h / b ratio can be controlled by the type and amount of monomer in the fine particles, the reaction temperature and time during monomer polymerization, the reaction medium and pH of the reaction system, and the type of dispersant and concentration of monomer in the reaction system. h / b can be increased, for example, by raising the reaction temperature during monomer polymerization. Also, h / b can be decreased by lowering the reaction temperature during monomer polymerization.
[0090] 3. Organosilicon Compound In the present disclosure, the fine particles contain an organosilicon compound. When the fine particles contain the organosilicon compound, affinity can be obtained with each of the outer surface of the developing roller which is a resin and the silica particles which are a silicon compound. In addition to the shape of the fine particles, this affinity makes it easy to maintain a state where the contact area between the fine particles and the outer surface of the developing roller is large, and adhesion and accumulation of bleed matter on the outer surface of the developing roller can be suppressed. Furthermore, even when the fine particles mesh with the silica particles, an appropriate chemical adhesive force easily acts due to the affinity between the fine particles and the silica particles, and the fine particles are susceptible to the shearing force required to be removed from the outer surface of the developing roller.
[0091] Further, in the present disclosure, the fine particles preferably contain at least one selected from the group consisting of a structure represented by the following formula (D), a structure represented by the following formula (T), and a structure represented by the following formula (Q). The fine particles more preferably contain at least one selected from the group consisting of the structure represented by the following formula (D) and the structure represented by the following formula (T), and further preferably contain the structure (T3 unit structure) represented by the following formula (T). For example, the fine particles are preferably an organosilicon polymer. (Ra)(Rb)Si(O 1 / 2 )2 Formula (D) Rc-Si(O 1 / 2 )3 Formula (T) Si(O 1 / 2 )4 Formula (Q)
[0092] (Ra, Rb and Rc in formula (D), formula (T) and formula (Q) each represent an organic group bonded to a silicon atom.) When the fine particles contain at least one selected from the group consisting of the structures represented by formula (D), formula (T) and formula (Q), the balance of affinity with the outer surface of the developing roller and the silica particles as an external additive is more excellent.
[0093] Ra, Rb, and Rc are preferably organic groups having 1 to 8 carbon atoms (preferably 1 to 6 carbon atoms, more preferably 1 to 3 carbon atoms). In particular, when Ra, Rb, and Rc are alkyl groups (more preferably methyl groups), the hardness of the fine particles increases, making it difficult for bleed material to penetrate into the fine particles and suppressing direct adhesion and accumulation on the outer surface of the developing roller, which is therefore preferable.
[0094] Furthermore, the content of the structure represented by formula (D), formula (T), and / or formula (Q) in the fine particles (preferably the structure represented by formula (D) and the structure represented by formula (T), more preferably the structure represented by formula (T)) is preferably 50 mol% or more, and more preferably 70 mol% or more.
[0095] The presence of organosilicon compounds in the fine particles can be confirmed by FTIR. Furthermore, the siloxane polymer moiety (-Si(O)) in the structures represented by formulas (D), (T), and (Q) 1 / 2 ) * The existence of (* is an integer between 2 and 4) indicates the presence of fine particles 29 This can be confirmed by Si-NMR measurement. Furthermore, the presence of Ra, Rb, and Rc in equations (D) and (T) indicates the presence of fine particles. 13 This can be confirmed by measuring with 1C-NMR.
[0096] Fine particles can be produced, for example, by condensation polymerization of an organosilicon compound. For example, the fine particles are a condensation polymer of an organosilicon compound. Here, the organosilicon compound is at least one selected from the group consisting of an organosilicon compound having a structure represented by the following formula (ZD), an organosilicon compound having a structure represented by the following formula (ZT), and an organosilicon compound having a structure represented by the following formula (ZQ). An organosilicon compound having a structure represented by formula (ZT) is more preferred. [ka]
[0097] (In formulas (ZD), (ZT), and (ZQ), Ra, Rb, and Rc represent organic groups bonded to silicon (preferably alkyl groups having 1 to 8 carbon atoms (preferably 1 to 6, more preferably 1 to 3)). 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9 Each of these independently represents a halogen atom, a hydroxyl group, an acetoxy group, or an alkoxy group (preferably having 1 to 3 carbon atoms, more preferably 1 or 2 carbon atoms).
[0098] Examples of organosilicon compounds having the structure represented by formula (ZD) include the following: Dimethyldimethoxysilane, dimethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-mercaptopropylmethyldimethoxysilane.
[0099] Examples of organosilicon compounds having the structure represented by formula (ZT) include the following: Vinyltrimethoxysilane, vinyltriethoxysilane, vinyldiethoxymethoxysilane, vinylethoxydimethoxysilane, vinyltrichlorosilane, vinylmethoxydichlorosilane, vinylethoxydichlorosilane, vinyldimethoxychlorosilane, vinylmethoxyethoxychlorosilane, vinyldiethoxychlorosilane, vinyltriacetoxysilane, vinyldiacetoxymethoxysilane, vinyldiacetoxyethoxysilane, vinylacetoxydimethoxysilane, vinylacetoxymethoxyethoxysilane, vinylacetoxydiethoxysilane, vinyltrihydroxysilane, vinylmethoxydihydroxysilane Trifunctional vinylsilanes such as vinylethoxydihydroxysilane, vinyldimethoxyhydroxysilane, vinylethoxymethoxyhydroxysilane, vinyldiethoxyhydroxysilane; allyltrimethoxysilane, allyltriethoxysilane, allyldiethoxymethoxysilane, allylethoxydimethoxysilane, allyltrichlorosilane, allylmethoxydichlorosilane, allylethoxydichlorosilane, allyldimethoxychlorosilane, allylmethoxyethoxychlorosilane, allyldiethoxychlorosilane, allyltriacetoxysilane, allyldiacetoxymethoxysilane, allyldiacetoxyethyl Trifunctional allylsilanes such as silane, allylacetoxydimethoxysilane, allylacetoxymethoxyethoxysilane, allylacetoxydiethoxysilane, allyltrihydroxysilane, allylmethoxydihydroxysilane, allylethoxydihydroxysilane, allyldimethoxyhydroxysilane, allylethoxymethoxyhydroxysilane, allyldiethoxyhydroxysilane; trifunctional styrylsilanes such as p-styryltrimethoxysilane; methyltrimethoxysilane, methyltrieth Xysilane, methyldiethoxymethoxysilane, methylethoxydimethoxysilane, methyltrichlorosilane, methylmethoxydichlorosilane, methylethoxydichlorosilane, methyldimethoxychlorosilane, methyldiethoxychlorosilane, methyltriacetoxysilane, methyldiacetoxymethoxysilane, methyldiacetoxyethoxysilane, methylacetoxydimethoxysilane, methylacetoxymethoxyethoxysilane, methylacetoxydiethoxysilane Trifunctional methylsilanes such as methyltrihydroxysilane, methylmethoxydihydroxysilane, methylethoxydihydroxysilane, methyldimethoxyhydroxysilane, methylethoxymethoxyhydroxysilane, methyldiethoxyhydroxysilane; trifunctional ethylsilanes such as ethyltrimethoxysilane, ethyltriethoxysilane, ethyltrichlorosilane, ethyltriacetoxysilane, ethyltrihydroxysilane; trifunctional propylsilanes such as propyltrimethoxysilane, propyltriethoxysilane, propyltrichlorosilane, propyltriacetoxysilane, propyltrihydroxysilane; trifunctional butylsilanes such as butyltrimethoxysilane, butyltriethoxysilane, butyltrichlorosilane, butyltriacetoxysilane, butyltrihydroxysilane; trifunctional hexylsilanes such as hexyltrimethoxysilane, hexyltriethoxysilane, hexyltrichlorosilane, hexyltriacetoxysilane, hexyltrihydroxysilane;Trifunctional phenylsilanes such as phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrichlorosilane, phenyltriacetoxysilane, and phenyltrihydroxysilane; trifunctional epoxysilanes such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; trifunctional methacrylsilanes such as 3-methacryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; trifunctional acrylsilanes such as 3-acryloxypropyltrimethoxysilane; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2 Trifunctional aminosilanes such as -(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; trifunctional ureidosilanes such as 3-ureidopropyltriethoxysilane; trifunctional chloropropylsilanes such as 3-chloropropyltrimethoxysilane; trifunctional mercaptosilanes such as 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; trifunctional sulfidosilanes such as bis(triethoxysilylpropyl)tetrasulfide; and trifunctional isocyanatesilanes such as 3-isocyanatetopropyltriethoxysilane.
[0100] Examples of organosilicon compounds having the structure represented by formula (ZQ) include the following: Tetraalkoxysilanes such as tetramethoxysilane and tetraethoxysilane; tetraalkylcarboxysilanes such as tetraacetoxysilane; tetrahalosilanes such as tetrachlorosilane.
[0101] Furthermore, the fine particles may also contain, in addition to the condensed polymers of the above-mentioned organosilicon compounds, organosilicon compounds having one reactive group per molecule (monofunctional silanes), or condensed polymers of other difunctional, trifunctional, and tetrafunctional silanes. Examples of these compounds include: The following are some examples.
[0102] Hexamethyldisilazane, trimethylsilyl chloride, triethylsilyl chloride, triisopropylsilyl chloride, t-butyldimethylsilyl chloride, N,N'-bis(trimethylsilyl)urea, N,O-bis(trimethylsilyl)trifluoroacetamide, trimethylsilyltrifluoromethanesulfonate, 1,3-dichloro-1,1,3,3-tetraisopropyldisiloxane, trimethylsilylacetylene, hexamethyldisilane, tetraisocyanatesilane, methyltriisocyanatesilane, vinyltriisocyanatesilane.
[0103] Furthermore, the fine particles may also contain condensed polymers of organotitanium compounds and organoaluminum compounds, in addition to the condensed polymers of the organosilicon compounds mentioned above.
[0104] 4. Method for producing fine particles The following describes specific methods for manufacturing microparticles, but these are not the only methods. An example of a method for producing fine particles is the sol-gel method. The sol-gel method involves the use of metal alkoxides M(OR) n This method uses (M: metal, O: oxygen, R: hydrocarbon, n: oxidation state of the metal) as a starting material, hydrolyzes and condenses in a medium, and then gels after passing through a sol state. If the fine particles contain a structure represented by formula (D), (T), or (Q), then metal alkoxide M(OR) n For this purpose, organosilicon compounds having a structure represented by formula (ZD), (ZT), or (ZQ) may be used. This manufacturing method allows for the production of functional materials in various forms, such as surface layers, fibers, bulk materials, and fine particles, from a liquid phase at low temperatures. Furthermore, because the sol-gel method starts from a solution and forms the material by gelling that solution, it can create a variety of microstructures and shapes. The microstructure and shape can be adjusted by the type and amount of monomer, reaction temperature, reaction time, reaction medium and pH of the reaction system, and the type and concentration of dispersant.
[0105] Generally, in sol-gel reactions, the bonding state of the resulting metalloxane bond (MOM) differs depending on the acidity of the reaction medium. Specifically, when the reaction medium is acidic, a hydrogen ion electrophilically adds to the oxygen of one of the reactants (e.g., an alkoxy group). Then, the oxygen atom in the water molecule coordinates to the metal atom, and a hydroxyl group is formed through a substitution reaction. When sufficient water is present, one hydrogen ion attacks one oxygen atom of a reactive group (e.g., an alkoxy group). As the reaction progresses, the hydrogen ion content and reactive groups in the medium decrease, slowing down the substitution reaction to hydroxyl groups. Therefore, a condensation polymerization reaction occurs before all the reactive groups attached to the metal atoms are hydrolyzed, making it relatively easy to generate one-dimensional linear polymers or two-dimensional polymers.
[0106] On the other hand, when the medium is alkaline, hydroxide ions add to the metal atom, proceeding via a five-coordinate intermediate. As a result, all reactive groups (e.g., alkoxy groups) are easily eliminated and readily replaced by hydroxyl groups. In particular, when a metal compound with three or more reactive groups on the same metal atom is used, hydrolysis and condensation polymerization occur three-dimensionally, forming an organometallic polymer (e.g., an organosilicon polymer) with many three-dimensional crosslinks. Furthermore, this reaction is completed in a short time.
[0107] Therefore, in order to form fine particles made of organometallic polymers, it is preferable to carry out the sol-gel reaction in an alkaline state, and when manufactured in an aqueous medium, it is preferable that the pH be 8.0 or higher. This results in higher strength and superior durability. It can form fine particles. Examples of aqueous media include: water, or a mixed solvent of water and alcohols such as methanol, ethanol, or propanol.
[0108] Furthermore, in order to make the fine particles solid and substantially hemispherical in shape, and to control the average number of particles with the longest diameter w on a substantially flat surface to 10 nm or more and 400 nm or less, it is preferable to manufacture them by dispersing an organometallic compound (e.g., an organosilicon compound) and a substrate in a medium such as an aqueous medium.
[0109] First, the substrate is dispersed in a medium to obtain a substrate dispersion. It is preferable to disperse the substrate at a concentration such that the solid content of the substrate is 5% by mass or more and 40% by mass or less relative to the total volume of the substrate dispersion. A dispersion stabilizer, as described later, may be used as appropriate. It is also preferable to adjust the temperature of the substrate dispersion to 35°C or higher. Furthermore, it is preferable to adjust the pH of the substrate dispersion to a pH at which the condensation of the organosilicon compound is less likely to proceed. The pH at which the condensation of the organosilicon compound is less likely to proceed varies depending on the type of organosilicon compound, but it is preferable to adjust it to within ±0.5 of the pH at which the reaction is least likely to proceed. Note that it is not necessary to completely disperse the substrate in the medium. For example, if the substrate is a flat plate, the plate may be propped up in the reaction vessel and the condensation may proceed on the substrate.
[0110] Next, it is preferable to use an organosilicon compound that has undergone hydrolysis treatment. For example, the organosilicon compound may be hydrolyzed in a separate container. The concentration of the hydrolysis treatment is preferably 40 to 500 parts by mass of water from which ions have been removed, such as ion-exchanged water or RO water, when the amount of organosilicon compound is 100 parts by mass, and more preferably 100 to 400 parts by mass of water. The conditions for the hydrolysis treatment are preferably a pH of 1.0 to 7.0 (more preferably 2.0 to 4.0), a temperature of 15 to 80°C (more preferably 40 to 70°C), and a time of 1 to 600 minutes (more preferably 30 to 300 minutes).
[0111] Then, the hydrolyzed organosilicon compound is added to the substrate dispersion. The substrate dispersion and the hydrolyzed organosilicon compound are stirred and mixed, and the mixture is held at a temperature of preferably 35°C or higher (more preferably 40-60°C) for 3 minutes to 120 minutes. After that, the pH is adjusted to a pH suitable for condensation (preferably pH 6.0 or higher or pH 3.0 or lower, more preferably pH 8.0 or higher (even more preferably 8.5-9.5)), and the organosilicon compound is rapidly condensed. The mixture is then held at a temperature of preferably 35°C or higher (more preferably 40-60°C) for 60 minutes or more to form fine particles made of organosilicon polymers, such as organosilicon polymers, on the substrate surface.
[0112] Then, the substrate, on which fine particles have been formed on its surface, is stirred and mixed using a medium in which the substrate has high solubility and the fine particles have low solubility, to dissolve only the substrate. Since the solubility differs depending on the material of the substrate and the type of medium, the solid content concentration of the substrate, stirring time, and temperature are set to a range in which the substrate is sufficiently dissolved. Subsequently, the fine particles can be separated by methods such as centrifugation and dried to obtain solid, substantially hemispherical fine particles. If the solubility of the substrate is low, the fine particles may be separated by simply withdrawing them from the reaction vessel and peeling them off the substrate.
[0113] When manufacturing fine particles, suitable substrates from the viewpoint of separation from the fine particles include various flat plates such as metals, glass, and ceramics, as well as resin particles. Among these, resin particles with a low degree of crosslinking and good solubility are particularly preferred. When the size of the resin particles (e.g., number-average particle size) is 1 to 100 μm (more preferably 5 to 15 μm), the particle size of the substrate becomes several tens of times or more the particle size of the fine particles, making it easy to manufacture fine particles with a substantially hemispherical shape having both a roughly flat and a curved surface. The material of the resin particles is not particularly limited, but polymethyl methacrylate (PMMA) particles, polystyrene fine particles, etc., manufactured by soap-free emulsion polymerization are preferred.
[0114] Furthermore, when dispersing the organosilicon compound and the substrate in a medium, known surfactants, inorganic and organic dispersants may be used as dispersion stabilizers.
[0115] Examples of surfactants include the following: (1) Anionic surfactants: alkyl sulfates such as sodium lauryl sulfate; polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate; sulfonates such as sodium dodecylbenzenesulfonate and sodium alkylnaphthalenesulfonate; higher fatty acid salts such as sodium stearate and sodium laurate.
[0116] (2) Cationic surfactants: Quaternary ammonium salts such as dodecylammonium bromide, dodecyltrimethylammonium bromide, dodecylpyridinium chloride, dodecylpyridinium bromide, hexadecyltrimethylammonium bromide, lauryltrimethylammonium chloride, alkylbenzyldimethylammonium chloride.
[0117] (3) Nonionic surfactants: Polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether and polyoxyethylene oleyl ether; polyoxyalkylene derivatives such as polyoxyethylene alkyl ether; sorbitan fatty acid esters such as sorbitan monolaurate and sorbitan monostearate; glycerin fatty acid esters such as glycerol monostearate; polyoxyethylene fatty acid esters such as polyethylene glycol monolaurate.
[0118] Other examples of inorganic dispersants include the following: Trivalent aluminum salts such as aluminum chloride, aluminum sulfate, aluminum hydroxide, aluminum phosphate, and polyaluminum chloride; trivalent and divalent iron salts such as iron(III) chloride, iron(III) sulfate, iron(III) hydroxide, iron(II) chloride, iron(II) sulfate, iron(II) hydroxide, polyferrous sulfate, and polysilica iron; divalent magnesium salts such as magnesium chloride, magnesium sulfate, magnesium hydroxide, magnesium phosphate, and magnesium carbonate; divalent calcium salts such as calcium chloride, calcium sulfate, tricalcium phosphate, calcium hydrogen phosphate, dihydrogen calcium phosphate, calcium hydroxide, hydroxyapatite, calcium carbonate, and calcium metasilicate; divalent cobalt salts such as cobalt chloride and cobalt sulfate; divalent zinc salts such as zinc phosphate; divalent barium salts such as barium sulfate; silicate minerals such as bentonite; and metal oxides such as silica and alumina.
[0119] In addition, the following can be mentioned as organic dispersants. Polyvinyl alcohol, gelatin, methylcellulose, methylhydroxypropylcellulose, ethylcellulose, sodium salt of carboxymethylcellulose, starch. These dispersion stabilizers are appropriately selected based on the material of the substrate and their interaction with organometallic compounds. These dispersion stabilizers may be used individually or in combination.
[0120] 5. Method for manufacturing a developing roller in which fine particles are attached to the outer surface. The following describes a method for manufacturing a developing roller in which fine particles adhere to the outer surface, but it is not limited to these methods. A developing roller having a plurality of fine particles attached to its outer surface according to one aspect of this disclosure can be obtained by attaching the fine particles to the developing roller. The method for attaching the fine particles to the outer surface of the developing roller is not particularly limited as long as it is a method that can attach the fine particles to the area of the outer surface of the developing roller that is in contact with the toner supply roller.
[0121] One method for adhering fine particles to the outer surface of a developing roller is to fill a developing device equipped with a toner supply roller and a toner regulating member, which is used in electrophotographic equipment, with fine particles, assemble a developing roller that does not have fine particles attached to it, and then drive the developing device. In this method, the fine particles are supplied to the developing roller by the toner supply roller and rubbed against the outer surface of the developing roller by the toner supply roller and toner regulating member. As the developing roller rotates repeatedly during this process, the fine particles tend to adhere stably with their nearly flat portions in contact with the outer surface of the developing roller. Furthermore, this method allows for repeated rubbing of the fine particles against the developing roller, making it easier for the approximately flat particles with a large contact area to adhere to the outer surface of the developing roller. The amount of fine particles adhering to the outer surface of the developing roller can be varied by changing the amount of fine particles packed into the developing device and the operating time of the developing device.
[0122] Furthermore, if the substrate used to manufacture the fine particles is in the form of particles, and the fine particles peel off from the outer surface of the substrate, the fine particles may be replaced with particles formed on the outer surface of the substrate and loaded into the developing apparatus, and the apparatus may be driven in the same manner to cause the fine particles to adhere to the outer surface of the developing roller.
[0123] Furthermore, the amount of fine particles adhering to the outer surface of a developing roller according to one aspect of this disclosure can be confirmed, for example, based on the concentration of silicon element (atomic%) measured by EDS. In the measurement method described later, it is preferable that the amount of fine particles based on the concentration of Si element on the outer surface of the surface layer to which the fine particles are adhering is 3.0 atomic% or more. More preferably, it is 3.0 to 20.0 atomic%, even more preferably 5.0 to 15.0 atomic%, and even more preferably 8.0 to 12.0 atomic%. Within the above range, the gaps caused by fine particles on the outer surface of the developing roller are almost eliminated, which is preferable because it further suppresses the direct adhesion and accumulation of bleed material on the outer surface of the developing roller.
[0124] The amount of fine particles adhering to the outer surface of the developing roller can be controlled, for example, by filling the developing device with fine particles and driving the device to adhere them to the developing roller, depending on the amount of fine particles filled and the operating time of the developing device. Excess fine particles may also be removed by air blowing or other means.
[0125] <Toner supply roller> A toner supply roller according to one aspect of this disclosure preferably has a conductive substrate and a foamed elastic layer on the substrate. When a developing apparatus comprising a toner supply roller and a developing roller is left in a high-temperature, high-humidity environment for a long period of time, bleed material from the toner supply roller, i.e., unreacted residue of resin components or ionic conductive agent components added to impart conductivity, may migrate from the toner supply roller to the developing roller at the contact position between the toner supply roller and the developing roller.
[0126] The foamed elastic layer of the toner supply roller is preferably conductive. The conductivity of the foamed elastic layer allows for the application of a potential difference between the toner supply roller and the developing roller by applying a high voltage from the high-voltage power supply of the electrophotographic apparatus. The voltage applied to the toner supply roller is preferably about +300V to -300V different from the voltage applied to the developing roller. For example, when using negatively charged toner, increasing the voltage difference to the positive side can increase the amount of toner stripped from the developing roller, while decreasing it to the negative side can increase the amount of toner supplied to the developing roller. By performing such voltage control according to the state of the developing device, the amount of toner supplied and stripped can be stabilized throughout the device's lifespan, making it possible to design a more durable developing device. Conductivity can be imparted to a foamed elastic layer by, for example, adding an ionic conductive agent to the resin of the foamed elastic layer. This can be done by the following method. In other words, it is preferable that the foamed elastic layer has an ionic conductive agent.
[0127] 1. Conductive substrate The substrate functions as a support member for the foamed elastic layer and as an electrode. The substrate is made of a metal or alloy such as aluminum, copper alloy, or stainless steel; iron plated with chromium or nickel; or a conductive material such as a conductive synthetic resin. The substrate is solid or hollow cylindrical.
[0128] 2. Foamed elastic layer The toner supply roller is required to uniformly supply toner to the surface of the developing roller, and characteristics such as the average cell diameter, number of cells, air permeability, and overall density of the foamed elastic layer are important. The physical properties of the foamed elastic layer 3 are not particularly limited, but it is preferable that they have values within the following numerical ranges, for example: average cell diameter of 100 μm or more and 500 μm or less, number of cells of 50 cells / inch or more and 300 cells / inch or less, air permeability of 0.5 L / min or more and 3.0 L / min or less, and density of 0.05 g / cm³ 3 More than 0.20g / cm 3 below. From the viewpoint of the above-mentioned properties and durability, the foamed elastic layer preferably contains a crosslinked urethane resin as a binder.
[0129] Furthermore, examples of ionic conductive agents for imparting conductivity to the foamed elastic layer include salts of Group 1 metals of the periodic table such as KCF3SO3, LiCF3SO3, LiN(CF3SO2)2, NaClO4, LiClO4, LiAsF6, LiBF4, NaSCN, KSCN, and NaCl; ammonium salts such as NH4Cl, (NH4)2SO4, and NH4NO3; salts of Group 2 metals of the periodic table such as Ca(ClO4)2 and Ba(ClO4)2; complexes of these salts with polyhydric alcohols such as 1,4-butanediol, ethylene glycol, polyethylene glycol, propylene glycol, and polypropylene glycol, or their derivatives; complexes of these salts with monools of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, polyethylene glycol monomethyl ether, and polyethylene glycol monoethyl ether; aliphatic sulfonates, alkyl sulfate esters, alkyl phosphate esters; and betaine salts. Furthermore, from the viewpoint of stability, the total content of the ionic conductive agent is preferably 0.1 parts by mass or more and 30 parts by mass or less per 100 parts by mass of the binder resin forming the foamed elastic layer.
[0130] The ionic conductive agent preferably contains fluorine as an anionic component. The ionic conductive agent is preferably at least one compound selected from the group consisting of KCF3SO3, LiCF3SO3, LiN(CF3SO2)2, LiAsF6, and LiBF4. Using a fluorine-based anion makes it easier to obtain high conductivity. Furthermore, if the anionic component is N(CF3SO2)2 - It is preferable if it is. The anionic components contained in the foamed elastic layer can be identified, for example, by ESI-MS or LC / MS.
[0131] 3. Others The foamed elastic layer may contain catalysts, foaming agents, foam stabilizers, and other auxiliary agents as needed. There are no particular restrictions on the catalyst, and various conventionally known catalysts can be appropriately selected and used. For example, amine catalysts, organometallic catalysts, and acid salt catalysts obtained by reducing the initial activity of the amine catalyst and organometallic catalyst can be used. One type of catalyst may be used, or two or more types may be used in combination.
[0132] There are no particular restrictions on the foaming agent; you may select and use any known foaming agent as appropriate. This can be achieved. In particular, water is suitable as a blowing agent because it reacts with polyisocyanate to generate carbon dioxide. Furthermore, using water in combination with other blowing agents does not impair the spirit of the present invention.
[0133] There are no particular restrictions on the foam stabilizer; it can be appropriately selected and used from among various conventionally known foam stabilizers. Other auxiliary agents may be used as needed, to the extent that they do not interfere with the effects of the present invention, including crosslinking agents, flame retardants, colorants, ultraviolet absorbers, antioxidants, conductive fillers, etc. As conductive fillers, carbon black; conductive metals such as aluminum and copper can be used.
[0134] 4. Method for manufacturing a toner supply roller The following describes, but is not limited to, a method for manufacturing a toner supply roller according to one aspect of this disclosure. There are no particular restrictions on the foaming method. Any method can be used, such as using a foaming agent or incorporating bubbles through mechanical stirring. The foaming ratio can be determined as appropriate and is not particularly restricted.
[0135] For example, by mixing the following materials and reacting them while foaming, a foamed elastic layer for a foamed elastic roller can be obtained. • As a material for forming the binder resin, Polyether polyols, polyester polyols, etc. Polyisocyanate Ionic conductive agents ·catalyst • Foam stabilizer • Foaming agent There are no particular restrictions on the temperature or time during mixing. The mixing temperature is usually in the range of 10°C to 90°C, preferably 20°C to 80°C. The mixing time depends on the structure of the mixing unit used, the rotation conditions, etc., but is usually between 1 second and 10 minutes, preferably between 3 seconds and 5 minutes.
[0136] There are no particular restrictions on the method of joining the substrate and the foamed elastic layer. Methods include pre-positioning the substrate inside a mold and then casting and curing the raw material mixture, or pre-forming the raw material mixture into a predetermined shape for the foamed elastic layer and then bonding it to the substrate. In either method, an adhesive layer can be provided between the substrate and the foamed elastic layer as needed. Known materials such as adhesives or hot-melt sheets can be used for this adhesive layer.
[0137] In the case of casting curing, a mold release agent may be applied to the inner wall of the mold beforehand. Known mold release agents can be used. Examples include water-based mold release agents containing wax components and silicone oil, and mold release agents in which fluororesin is dissolved in a fluorine-based solvent. An example of a fluororesin-containing mold release agent is a fluororesin-containing mold release agent (product name: Fluorosurf, FG-5093F130-0.5, manufactured by Fluorotechnology Co., Ltd.).
[0138] There are no particular restrictions on the method for forming the shape of the foamed elastic layer for use as a foamed elastic roller. For example, in addition to the method of casting into a mold of a predetermined shape as described above, the following methods can be used: cutting out predetermined dimensions from a block of polyurethane foam by machining, grinding to achieve predetermined dimensions, or a combination of these methods as appropriate.
[0139] <Toner> A toner according to one aspect of this disclosure comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin. The adhesion rate of the silica particles to the toner particles, as measured by a water washing method, is 50% or more.
[0140] 1. Toner particles Toner particles according to one aspect of this disclosure include a binder resin. They may also contain colorants and other components. As the binder resin, resins commonly used for toners (preferably amorphous) can be used. Specifically, styrene-acrylic resins (styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, etc.), polyester resins, epoxy resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, styrene-butadiene copolymers, mixed resins or composite resins thereof can be used.
[0141] The coloring agent is not particularly limited and any known coloring agent can be used. The toner particles may contain a release agent. The release agent is not particularly limited, and the following known substances can be used: paraffin wax, microcrystalline wax, petroleum waxes such as petrolatum and their derivatives, montan wax and its derivatives, hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch process, polyolefin waxes such as polyethylene and polypropylene and their derivatives, natural waxes such as carnauba wax and candelilla wax and their derivatives, higher aliphatic alcohols, fatty acids such as stearic acid and palmitic acid, or compounds thereof, acid amide waxes, ester waxes, ketones, hydrogenated castor oil and its derivatives, plant waxes, animal waxes, and silicone resins. Derivatives include oxides, block copolymers with vinyl monomers, and graft-modified products. These can be used individually or in combination.
[0142] The toner particles may contain a crystalline resin. The crystalline resin is not particularly limited, and known resins can be used. Specifically, examples include crystalline polyester resins and crystalline acrylic resins. The crystalline resin may also be a block polymer having crystalline and amorphous parts. The toner particles may contain a charge control agent, and known ones can be used.
[0143] Furthermore, an example of a toner particle manufacturing method is given below. (1) Suspension polymerization method: A polymerizable monomer composition containing polymerizable monomers capable of forming a binder resin, and optionally a mold release agent and a colorant, is granulated in an aqueous medium, and toner particles are obtained by polymerizing the polymerizable monomers. (2) Grinding method: Toner particles are obtained by melting and kneading a binder resin, and optionally a release agent and a coloring agent, and then grinding the mixture. (3) Dissolution suspension method: A binder resin, and optionally a release agent and a colorant, etc., are dissolved in an organic solvent to produce an organic phase dispersion. This dispersion is then suspended in an aqueous medium, granulated, polymerized, and the organic solvent is removed to obtain toner particles. (4) Emulsification Coagulation Polymerization Method: Toner particles are obtained by coagulating and associating binder resin particles, and, if necessary, release agent particles and colorant particles, in an aqueous medium.
[0144] Examples of aqueous media include: water; and mixed solvents of water and alcohols such as methanol, ethanol, and propanol.
[0145] 2. Silica particles Because the toner contains silica particles as an external additive, as described above, when the developing device is driven... The silica particles interlock with fine particles containing organosilicon compounds, making it easier to apply the shear force necessary to remove the fine particles from the outer surface of the developing roller. In addition, since silica particles are inorganic silicon compounds and have high hardness relative to resin, they can exhibit sufficient polishing properties on developing rollers with high hardness near the outer surface and on fine particles containing organosilicon compounds.
[0146] The silica particles relating to this disclosure can be any known silica fine particles, and may be either dry silica fine particles or wet silica fine particles. Preferably, they are wet silica fine particles obtained by the sol-gel method (hereinafter also referred to as sol-gel silica). Sol-gel silica exists in a spherical and monodisperse form, although some particles are partially coalesced.
[0147] When the full width at half maximum of the primary particle peak in the weight-based particle size distribution chart is 25 nm or less, there are fewer of these coalescing particles, increasing the uniform adhesion of silica fine particles to the toner particle surface and resulting in higher fluidity.
[0148] Furthermore, the adhesion rate of silica particles to toner particles, as measured by the water washing method, is 50% or more. A silica particle adhesion rate of 50% or more ensures that the adhesion force between the silica particles and toner particles exceeds the adhesion force between the fine particles and the developing roller, allowing the fine particles to be removed from the outer surface of the developing roller by the shear force generated when the silica particles interlock with the toner particles. The adhesion rate is preferably 50-95%, more preferably 65-92%, and even more preferably 70-92%.
[0149] The above-mentioned adhesion rate can be controlled by factors such as the order in which materials are added, the temperature during addition, and the rotation speed.
[0150] Furthermore, the number-average particle size of the primary silica particles is preferably 7 to 400 nm. A number-average particle size of 7 nm or more is preferable because it allows for easier interlocking with the fine particles, making it easier to apply the shear force necessary to remove the fine particles from the outer surface of the developing roller. A number-average particle size of 400 nm or less is also preferable because it allows for easier interlocking with the fine particles and makes it easier to stably fix the silica particles to the binder resin, making it easier to apply the shear force. Furthermore, the number-average particle size of the primary silica particles is more preferably 7 to 100 nm, and even more preferably 10 to 30 nm. The number-average particle size of the primary silica fine particles produced by the sol-gel method can be controlled by the reaction temperature in the hydrolysis and condensation reaction steps, the dropping rate of the alkoxysilane, the weight ratio of water, organic solvent, and catalyst, and the stirring speed.
[0151] Furthermore, the silica particle content in the toner is preferably 0.5 to 3.0 parts by mass per 100 parts by mass of toner particles. More preferably, it is 1.0 to 2.0 parts by mass. When the silica particle content is 0.5 parts by mass or more, it interlocks with the fine particles, making it easier to remove the fine particles from the outer surface of the developing roller. When it is 3.0 parts by mass or less, the presence of excess silica particles on the outer surface of the toner particles suppresses rolling between them and the fine particles, causing the toner and fine particles to interlock and making it easier to remove the fine particles from the outer surface of the developing roller.
[0152] The silica nanoparticles obtained in this way are usually hydrophilic and have many surface silanol groups. Therefore, when used as an external additive for toner, it is preferable to hydrophobize the surface of the silica nanoparticles. Methods for hydrophobic treatment include removing the solvent from the silica sol suspension, drying it, and then treating it with a hydrophobic agent, and directly adding the hydrophobic agent to the silica sol suspension and treating it simultaneously with drying. From the viewpoint of controlling the full width at half maximum of the particle size distribution and the amount of water adsorbed by saturation, the method of directly adding the hydrophobic agent to the silica sol suspension is preferred.
[0153] Examples of hydrophobic treatment agents include the following: γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)γ-aminopropyltrimethoxysilane hydrochloride, hexamethyldisilazane, methyltrimethoxysilane, butyltrimethoxysilane, isobutyltrimethoxysilane, hexyltoerymethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, phenyltrimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, methyltriethoxysilane, butyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltriethoxysilane, dodecyltoethoxysilane, phenyltriethoxysilane, o-methylphenyltriethoxysilane, p-methylphenyltriethoxysilane.
[0154] Furthermore, the silica microparticles may be crushed in order to facilitate monodispersion of the silica microparticles on the surface of the toner particles and to ensure a stable interlocking effect with the microparticles.
[0155] 3. Hydrotalcite particles In this case, if the toner supply roller contains an ionic conductive agent in its foamed elastic layer, it is preferable that the toner contains hydrotalcite particles as an external additive. This allows for more rapid suppression of band images. Hydrotalcite has ion exchange capabilities. Therefore, even if the ion-conductive agent component bleeds from the toner supply roller and adheres to fine particles or the outer surface of the developing roller in the gaps between the fine particles, it is thought that the ion-conductive agent component is removed during the polishing process by ion exchange with the hydrotalcite particles when polished by the toner containing hydrotalcite particles as an external additive.
[0156] Hydrotalcite particles represented by the following structural formula (1) can be used. 2+ y M3+ x (OH)2A n- (x / n) ·mH2O formula (1) Here, 0 <x≦0.5、y=1-x、m≧0である。 M 2+ , and M 3+ These represent divalent and trivalent metals, respectively. M 2+ It is preferable that the element is at least one divalent metal ion selected from the group consisting of Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe. M 3+ It is preferable that is at least one trivalent metal ion selected from the group consisting of Al, B, Ga, Fe, Co, and In. A n- It is an n-valent anion, CO3 2- , OH - Cl - , I - F - , Br - SO4 2- , HCO3 - CH3COO - , and NO3 - These are examples, and there may be one or more species.
[0157] Furthermore, if the ionic conductive agent contains a fluorine-based anion, it is more preferable that the toner has hydrotalcite particles containing fluorine as an external additive. As mentioned above, fluorine-based anions readily exhibit excellent conductivity and are therefore suitably used, for example, in toner supply rollers for highly durable developing equipment. In contrast, it is thought that hydrotalcite, by containing fluorine internally, has improved affinity for fluorine-based anions, resulting in superior ion exchange capacity for fluorine-based anions.
[0158] Hydrotalcite particles containing fluorine can be produced by introducing fluoride ions into the interlayer (intercalation) through anion exchange. By introducing an appropriate amount of fluorine into hydrotalcite particles, it is possible to achieve excellent ion exchange capacity for the above-mentioned fluorine-based anions.
[0159] The ratio of the atomic concentration of magnesium to aluminum in hydrotalcite particles, Mg / Al (elemental ratio), obtained from the main component mapping of hydrotalcite particles by STEM-EDS mapping analysis of toner, is preferably 1.5 to 4.0, and more preferably 1.6 to 3.8. The Mg / Al ratio can be controlled by adjusting the amount of raw materials used in hydrotalcite production. The atomic concentration of magnesium is preferably 3.00 to 20.00 atomic%, more preferably 4.00 to 16.00 atomic%, and even more preferably 9.00 to 14.00 atomic%.
[0160] The number-average particle size of the primary particles of the hydrotalcite particles is preferably 60 to 1000 nm, more preferably 60 to 800 nm, and even more preferably 200 to 600 nm.
[0161] Furthermore, the presence or absence of fluorine and aluminum in hydrotalcite particles can be confirmed by STEM-EDS mapping analysis of the toner. In line analysis during STEM-EDS mapping analysis of the toner, the presence of fluorine within the hydrotalcite particles is preferable, and the presence of both fluorine and aluminum is more preferable.
[0162] Furthermore, it is preferable that the ratio of the atomic concentration of fluorine to aluminum in hydrotalcite particles, F / Al (elemental ratio), obtained from the main component mapping of hydrotalcite particles by STEM-EDS mapping analysis of the toner, is between 0.01 and 0.60. A F / Al ratio of 0.01 or higher is preferable because it improves affinity with fluorine-based anions. A F / Al ratio of 0.60 or lower is preferable because it facilitates rapid ion exchange of fluorine-based anion components. The elemental ratio F / Al is more preferably 0.02 to 0.60, and even more preferably 0.04 to 0.30. F / Al can be controlled by adjusting the fluorine concentration during the production of hydrotalcite particles.
[0163] The mixer used to add the above-mentioned external additives to the toner particles is not particularly limited, and any known mixer, whether dry or wet, can be used. Examples include the FM mixer (manufactured by Nippon Coke Industries Co., Ltd.), the Super Mixer (manufactured by Kawata Co., Ltd.), the Nobilta (manufactured by Hosokawa Micron Corporation), and the Hybridizer (manufactured by Nara Machinery Co., Ltd.). To control the coating state of the external additive, the rotation speed, processing time, and water temperature and volume of the jacket of the above-mentioned external additive device can be adjusted to prepare the toner. For example, the mixing time is preferably 1 to 60 minutes, more preferably 3 to 10 minutes. The jacket temperature is preferably 5 to 40°C, more preferably 7 to 15°C.
[0164] The hydrotalcite particle content is preferably 0.1 to 1.0 parts by mass, and more preferably 0.1 to 0.3 parts by mass, per 100 parts by mass of toner particles. Adding 0.1 parts by mass or more allows the ion conductive agent component from the toner supply roller to be efficiently removed by ion exchange with the hydrotalcite particles.
[0165] 4. Other external additives In one aspect of this disclosure, the toner may contain, in addition to the silica particles and hydrotalcite particles mentioned above, titanium dioxide, strontium titanate, stearyl dioxide, etc., to the extent that they do not impair the effects of this disclosure. Known particles such as zinc oxide can be used as external additives.
[0166] <Developing equipment> Figure 1 is a cross-sectional view perpendicular to the longitudinal direction of a developing apparatus according to one embodiment of the present disclosure. The developing apparatus 1 shown in Figure 1 includes a developing roller 2 on which fine particles 4 are attached to the outer surface, a toner supply roller 3, a developing container 6 that houses a developing blade 5, and a toner container 8 that houses toner 7. The developing roller 2 is assembled to be in contact with the toner supply roller 3 and the developing blade 5.
[0167] In the developing device 1 before initial use, the toner 7 may be present inside the developing container 6 or at the contact position between the developing roller 2 and the toner supply roller 3, to the extent that it does not hinder the effects of this disclosure. However, as shown in Figure 1, it is preferable that the toner 7 is separated from the developing container 6 by a sealing member 9 or the like. In the developing device 1 in which the toner 7 is separated from the developing container 6 by a sealing member 9, the sealing member 9 is removed before the development device 1 is put into use, so that the toner 7 flows into the developing container 6 through an opening provided in the toner container 8.
[0168] The development process in the developing apparatus 1 is described below. Toner 7 is applied onto the developing roller 2 by a rotatably supported toner supply roller 3. The toner 7 applied to the developing roller 2 is rubbed against the developing blade 5 by the rotation of the developing roller 2. Here, the developing blade restricts the toner 7 so that an appropriate amount of toner 7 is uniformly coated onto the developing roller 2.
[0169] As described above, the conductivity of the toner supply roller 3 makes it possible to apply a potential difference between the toner supply roller 3 and the developing roller 2 by applying a high voltage from the high-voltage power supply of the electrophotographic device. It is preferable that the voltage applied to the toner supply roller 3 be approximately +300V to -300V different from the voltage applied to the developing roller 2. For example, when using negatively charged toner, increasing the voltage difference to the positive side can increase the amount of toner 7 stripped from the developing roller 2. Conversely, increasing the voltage difference to the negative side can increase the amount of toner 7 supplied to the developing roller 2. By performing such voltage control according to the state of the developing device 1, the supply and stripping amounts of toner 7 can be stabilized throughout extended use.
[0170] Furthermore, the developing blade 5 can be a member with a rubber elastic body fixed to a metal sheet, a springy member such as a thin sheet of SUS or phosphor bronze, or a member with resin or rubber laminated on its surface. In addition, by creating a potential difference between the developing blade 5 and the developing roller 2, it is possible to control the toner layer on the developing roller 2, and for this purpose, it is preferable that the developing blade 5 is conductive. The voltage applied to the developing blade 5 is preferably different from the voltage applied to the developing roller, for example, when negatively charged toner is used, to about 0V to -300V.
[0171] <Method for cleaning the outer surface of the developing roller> A cleaning method according to one aspect of this disclosure is performed in conjunction with the use of the developing apparatus, i.e., the initial sequence drive of the developing apparatus by the electrophotographic apparatus, for example, the drive to supply toner to the developing roller and coat it during initial use, or the drive for image output. Through these drives, the toner in the developing container is supplied to the outer surface of the developing roller by the drive of the toner supply roller and the developing roller. Then, the outer surface of the developing roller and the toner are rubbed against each other by contact members such as the toner supply roller, developing blade, and photoreceptor described later, causing multiple fine particles adhering to the outer surface of the developing roller's surface layer to come into contact with the toner. The contact between the fine particles and the toner scrapes off the particles, removing them from the surface. By combining a developing roller, fine particles, and toner that satisfy the features of this disclosure, bleed material from the toner supply roller adheres to the roller during these processes. The fine particles are effectively removed from the outer surface of the developing roller.
[0172] <Process cartridges and electrophotographic image forming apparatus> The process cartridge relating to this disclosure is a process cartridge that is detachably attached to the main body of an electrophotographic image forming apparatus (electrophotographic apparatus) and has the developing apparatus described above. Furthermore, the electrophotographic apparatus according to this disclosure includes a photoreceptor and a developing device that is positioned in contact with the photoreceptor and supplies a developer to the electrostatic latent image formed on the photoreceptor, and the developing device is the developing device described above. Even with a developing device that has a developing roller that can suppress the occurrence of scratches and filming to an extremely high degree, it is possible to provide a process cartridge and electrophotographic apparatus that can suppress the occurrence of band images of the developing roller pitch due to being left in a high temperature and high humidity environment, and that can obtain highly durable and high-quality images.
[0173] Figure 6 shows one embodiment of a process cartridge. The process cartridge 61 shown in Figure 6 is detachable from an electrophotographic apparatus and includes a developing apparatus 1 according to this disclosure. Furthermore, the process cartridge 61 shown in Figure 6 is an all-in-one process cartridge that integrates a photoreceptor 62, a cleaning blade 63, a waste toner container 64, and a charging roller 65.
[0174] Figure 7 shows one embodiment of an electrophotographic apparatus. The electrophotographic apparatus shown in Figure 7 has a process cartridge 61 having a developing device 1, a photoreceptor 62, a cleaning blade 63, a waste toner container 64, and a charging roller 65 that can be detachably mounted. The photoreceptor 62, cleaning blade 63, waste toner container 64, and charging roller 65 may also be located in the main body of the electrophotographic apparatus.
[0175] The photoreceptor 62 rotates in the direction of the arrow and is uniformly charged by a charging roller 65 for charging the photoreceptor 62. An electrostatic latent image is formed on the surface of the photoreceptor 62 by a laser beam 71, which is an exposure means for writing an electrostatic latent image to the photoreceptor 62. The electrostatic latent image is developed by applying toner 7 by a developing device 1 that is positioned in contact with the photoreceptor 62, and is made visible as a toner image. The development is a so-called inversion development in which a toner image is formed in the exposed area. The visualized toner image on the photoreceptor 62 is transferred to an endless belt-shaped transfer belt 73 by a transfer roller 72, which is a transfer member. The transferred toner image is transported by the transfer belt 73 in the direction of the arrow to the secondary transfer position, and is transferred to the recording medium paper 75 fed by the paper feed roller 74 by a secondary transfer roller 76. The paper 75 with the transferred toner image is fixed by a fuser 77 and discharged from the device, completing the print operation.
[0176] The following describes the method for measuring physical properties. <Method for measuring the elastic moduli E1 and E2 of the first and second regions of the surface layer of the developing roller> A scanning probe microscope (SPM) (product name: MFP-3D-Origin, manufactured by Oxford Instruments) is used to measure the elastic moduli E1 and E2 of the first and second regions of the surface layer of the developing roller. The measurement sample is prepared as follows. The developing roller is cooled to -150°C, and a cryomicrotome (product name: UC-6, manufactured by Leica Microsystems) is used to cut out rubber flakes, revealing the cross-section of the surface layer, including the outer surface of the developing roller's surface layer, in the thickness direction.
[0177] The prepared rubber flakes are left for 24 hours in an environment of 23°C and 50% humidity. Next, the rubber flakes are placed on a silicon wafer, and the silicon wafer is set on the stage of the scanning probe microscope. Then, the cross-section of the surface layer of the rubber flakes is scanned with a probe (AC160 (product name), manufactured by Olympus). The conditions for the probe are as follows: Resonant frequency: 282 kHz (primary order) and 1.59 MHz (higher order). For the spring constant and invols constant of the probe, values measured for each probe using the above apparatus by the thermal noise method are used. Further, as other measurement conditions, the SPM measurement mode is set to the AM-FM mode, the free amplitude of the probe is 3 V, and the setpoint amplitude is 2 V (primary order) and 25 mV (higher order). Then, in a field of view of 5 μm × 5 μm including the outer surface of the developing roller surface layer, the scanning speed is 1 Hz, and the number of scanning points is 256 points vertically and 256 points horizontally.
[0178] Elastic modulus E1 of the matrix in the first region of the developing roller surface layer: For the first region of the developing roller surface layer (the region from the outer surface to a depth of 0.1 μm in the cross section in the thickness direction), 10 measurement points are designated, a force curve is acquired at each point based on the following conditions, and the elastic modulus is calculated by the Hertz theory. For the obtained results, the arithmetic mean of 8 points excluding the maximum value and the minimum value is determined. The selection of the matrix in the surface layer is performed by avoiding the conductive agent, filler, and the like contained in the surface layer. Specifically, the matrix is selected by designating the measurement points while avoiding fine particle-like portions in the phase image of the above field of view region. "Force Curve Acquisition Conditions" Force Dist: 500 nm Scan Rate: 1.0 Hz Show Markers: ON Show Tip: ON Withdraw During Movement: ON Imaging Mode: Contact Trigger Channel: DeflVolts Increasing: ON Relative: ON Trigger Point: 0.2 to 0.5 V "Elastic Modulus Calculation Conditions by Hertz Theory" Segment: Ext Tip Geometry: Sphere Radius: 8 nm Tip:Silicon<100> Sample Poisson:0.33
[0179] The above measurement is performed at a total of 9 locations, consisting of 3 equally spaced locations in the axial direction of the developing roller × 3 equally spaced locations in the circumferential direction, and the arithmetic mean value thereof is defined as the elastic modulus E1 of the matrix in the first region of the developing roller surface layer.
[0180] Elastic modulus E2 of the matrix in the second region of the developing roller surface layer: Except for the measurement location, the elastic modulus E2 of the matrix in the second region from a depth of 1.0 μm to 1.1 μm from the outer surface of the developing roller surface layer is measured in the same manner as the above elastic modulus E1.
[0181] <Method for confirming that fine particles have a substantially flat surface and a curved surface> The confirmation that the fine particles have a substantially flat surface and a curved surface is performed using a scanning transmission electron microscope (STEM). The sample for STEM observation is prepared as follows. First, fine particles are dispersed on the surface of a cover glass (Matsunami Glass Ind., Ltd., square cover glass; Square No. 1) from directly above the cover glass placed on a horizontal surface, and then the fine particles that have fallen onto the surface are rubbed against the surface. Next, using an osmium plasma coater (Filgen, Inc., OPC80T), an Os film (5 nm) and a naphthalene film (20 nm) are applied to the fine particles as protective films.
[0182] Next, a PTFE tube (inner diameter Φ1.5 mm × outer diameter Φ3 mm × 3 mm) is filled with a photocurable resin (trade name: D800, manufactured by JEOL Ltd.). Then, the cover glass is gently placed on the tube such that the surface on the side with the adhered fine particles is in contact with the photocurable resin in the tube. In this state, the photocurable resin in the tube is irradiated with light to cure the photocurable resin. Thereafter, the cover glass and the tube are removed to obtain a resin cylinder with fine particles embedded in the outermost surface portion. A thin flake sample with an exposed cross section along the longitudinal direction of the cylinder is cut out from the obtained cylinder. The cross-section of the thin section sample is cut using an ultrasonic ultramicrotome (Leica, UC7) to reveal a new cross-section parallel to the original cross-section. The cutting speed is set to 0.6 mm / s. The newly appearing cross-sections are observed one after another, and cutting is stopped when a cross-section showing the radial portion of the embedded microparticles is obtained. A sample with a film thickness of 100 nm, showing the cross-section with the radial portion of the embedded microparticles exposed, is then prepared for transmission electron microscopy (STEM) observation (hereinafter also referred to as the "STEM observation sample").
[0183] The obtained STEM samples were observed using STEM. The STEM equipment, observation method, and observation conditions used are as follows. Equipment: "Tecnai TF20XT" (product name, manufactured by FEI) The STEM probe size is 1 nm, and images are acquired with an image size of 1024 × 1024 pixels. In addition, the contrast of the brightfield image's Detector Control panel is adjusted to 1425, the brightness to 3750, and the contrast of the Image Control panel to 0.0, the brightness to 0.5, and the Gamma to 1.00 to acquire a STEM image including cross-sections of the microparticles in the sample for STEM observation. The image magnification is performed at 100,000 to 200,000 times.
[0184] From the obtained STEM images, the average number values of the particle ratios df / h, l1 / l2, and s1 / s2 are calculated using the image processing software ImageJ (developed by Wayne Rasband). The method for calculating df / h is explained below using Figures 5(a) to (c). First, use the Straight Line tool on the toolbar to select the scale bar in the observation conditions display area at the bottom of the image. With the scale bar selected, select Set Scale from the Analyze menu. A new window will open, and the pixel distance of the selected line will be entered in the Distance in Pixels field. Enter the value of the scale bar (e.g., 100) in the Known Distance field of the window, enter the unit of the scale bar (e.g., nm) in the Unit of Measurement field, and click OK to complete the scale setting.
[0185] Next, select ROI Manager from the Tools menu in Analyze, and check both Show All and Labels in the newly opened ROI Manager window.
[0186] Next, using the Straight Line tool on the toolbar, draw a virtual line Li connecting Pa and Pb, the two intersection points of line Lf, which originates from the approximately flat surface of the microparticles, and line Lc, which originates from the curved surface, as shown in Figures 5(a) to (c). With this done, select Add in the ROI Manager window. Then, draw a line A perpendicular to the virtual line Li as follows. Draw line A such that the distance d between the intersection point of line A and the virtual line Li and the intersection point of line A and line Lf, which originates from the approximately flat surface of the microparticles, is maximized, and then select Add. The distance d in line A is the maximum length df. Furthermore, draw a line Ls1 perpendicular to the virtual line Li as follows. Draw line Ls1 such that one of Da and Db below is maximized. Let Da be the distance between the intersection point Pc of the virtual line Li and line Ls1 and the intersection point Pe of the line Lc originating from the curved surface and line Ls1. Also, let Pd be the intersection point Pd of the line Lf originating from a roughly plane and line Ls1 and the line Lc originating from the curved surface and line Let Db be the distance between the intersection point Pe with Ls1 and the other point. Then, the maximum height h is the distance when either Da or Db is at its maximum. Draw a straight line Ls1 in this way and select Add. Afterward, selecting "Measure" in the ROI Manager window will perform the analysis. From the newly opened Results window, obtain the lengths corresponding to the maximum length df and maximum height h, and calculate the ratio df / h.
[0187] Next, using the Elliptical Selections tool on the toolbar, draw ellipses e1, which passes through the two intersection points of the approximate plane and curved surface of the microparticle (corresponding to Pa and Pb above) and is circumscribed around the curved surface of the microparticle, as shown in Figures 5(d) and (e), and ellipses e2, which passes through the two intersection points of the approximate plane and curved surface of the microparticle (corresponding to Pa and Pb above) and is circumscribed around the curved surface of the microparticle. With these ellipses in place, select Add in the ROI Manager window. Next, using the Straight Line tool on the toolbar, draw straight lines representing the major axis l1 and minor axis s1 of ellipse e1, and the major axis l2 and minor axis s2 of ellipse e2, as shown in Figures 5(f) and (g), and select Add. Then, select Measure in the ROI Manager window to perform the analysis. From the newly opened Results window, obtain the lengths corresponding to the major axis l1 of ellipse e1, the major axis l2 of ellipse e2, the minor axis s1 of ellipse e1, and the minor axis s2 of ellipse e2, and calculate the ratios l1 / l2 and s1 / s2.
[0188] The above procedure is performed for 100 particles to be evaluated, and the average values of the ratios df / h, l1 / l2, and s1 / s2 are calculated. Using the above method, (1) The average number of df / h is between 0.00 and 0.10. (2) Confirm that the average number of l1 / l2 is between 0.90 and 1.10, and that the average number of s1 / s2 is between 0.90 and 1.10. If it can be confirmed that both of the above conditions (1) and (2) are met, the fine particles are judged to have a substantially hemispherical shape having both a roughly flat surface and a curved surface.
[0189] <Confirmation method in which each of the fine particles has a substantially flat surface that is in surface contact with the outer surface of the surface layer, and a curved surface that constitutes at least a part of the convex portion> Whether the substantially flat surface of the fine particles is in contact with the outer surface of the developing roller is confirmed using a scanning electron microscope (SEM). First, a cross-sectional region including the outer surface of the developing roller is cut into thin slices using a diamond knife while being held at -110°C with a cryomicrotome (trade name: EMFC6, manufactured by Leica Microsystems). Further, a specimen of 100 μm square and 1 μm in width in the depth direction including the outer surface of the surface layer of the developing roller is prepared from the thin slice. The SEM apparatus, observation methods and conditions are as follows. Apparatus: Ultra-high resolution field emission scanning electron microscope S-4800 (hereinafter referred to as "S-4800") manufactured by Hitachi High-Technologies Corporation
[0190] (1) Specimen preparation A double-sided carbon tape for SEM (manufactured by Nissin EM Co., Ltd.) is attached to a specimen stage (15 mm × 6 mm aluminum specimen stage), and the thin slice sample of the developing roller described above is attached thereon. Thereafter, platinum deposition is performed at 15 mA for 15 seconds. The specimen stage is set in the specimen holder, and the height of the specimen stage is adjusted to 30 mm with a specimen height gauge.
[0191] (2) S-4800 observation condition setting Liquid nitrogen is poured into the anti-contamination trap attached to the housing of the S-4800 until it overflows, and the trap is left for 30 minutes. "PC-SEM" of the S-4800 is started, and fla shing (cleaning of the FE chip which is the electron source) is performed. Click the acceleration voltage display part of the control panel on the screen, press the [Flashing] button, and open the flashing execution dialog. Confirm that the flashing intensity is 2, and execute. Confirm that the emission current by flashing is 20 to 40 μA. Insert the specimen holder into the specimen chamber of the S-4800 housing. Press [Origin] on the control panel to move the specimen holder to the observation position. Click the acceleration voltage display to open the HV settings dialog, and set the acceleration voltage to [2.0kV] and the emission current to [10μA]. In the [Basic] tab of the operation panel, set the signal selection to [SE], select [L] for the SE detector, and enter the mode for observing backscattered electron images. Also in the [Basic] tab of the operation panel, set the probe current to [Normal], the focus mode to [UHR], and the WD to [8.0mm] in the electron optical system conditions block. Press the [ON] button on the acceleration voltage display of the control panel to apply the acceleration voltage.
[0192] (3) Focus adjustment Drag within the magnification display area of the control panel to set the magnification to 5000 (5k)x. Rotate the focus knob [COARSE] on the control panel until the image is somewhat in focus, then adjust the aperture alignment. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knob (X,Y) on the control panel to move the displayed beam to the center of the concentric circle.
[0193] Next, select [Aperture] and rotate the STIGMA / ALIGNMENT knobs (X,Y) one by one to stop or minimize the movement of the image. Close the Aperture dialog and focus using autofocus. Repeat this process two more times to focus. With the midpoint of the longest diameter of the observed particle aligned to the center of the measurement screen, drag within the magnification display area of the control panel to set the magnification to 10000 (10k) times. Rotate the focus knob [COARSE] on the control panel to adjust the aperture alignment once the image is somewhat in focus. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X,Y) on the control panel to move the displayed beam to the center of the concentric circle.
[0194] Next, select [Aperture] and rotate the STIGMA / ALIGNMENT knobs (X,Y) one by one to stop or minimize the image movement. Close the Aperture dialog and focus using autofocus. Then, set the magnification to 50000 (50k)x and adjust the focus using the focus knob and STIGMA / ALIGNMENT knob as described above, and focus again using autofocus. Repeat this process to focus.
[0195] (4) Save the image Brightness adjustment is performed in ABC mode, the size is set to 640 x 480 pixels, and the magnification is set to 10,000 to 50,000 (10 to 50k) times, and a cross-sectional image of the region including the fine particles and the outer surface of the developing roller is acquired and saved. From the obtained SEM image, it is confirmed that multiple fine particles are attached to the outer surface of the developing roller. Furthermore, from the SEM image, it is confirmed that the fine particles having substantially flat and curved surfaces identified by the method described above are in surface contact with the outer surface of the surface layer on the substantially flat side, and that these fine particles form a convex portion on the outer surface of the surface layer, with the curved surface constituting at least a part of the convex portion.
[0196] <Method for calculating the average number of particles with the longest diameter w on a nearly planar surface> The average number of the longest diameter w of the approximate plane is calculated using a scanning electron microscope (SEM). Sample preparation is as follows: A thin layer of conductive paste (product number 16053, manufactured by TED PELLA, Inc., PELCO Colloidal Graphite, Isopropanol base) is applied to the sample stage (aluminum sample stage 15mm x 6mm), and fine particles are attached on top of it. After removing excess particles from the sample stage by air blowing, platinum deposition is performed at 15mA for 15 seconds. The sample stage is set in the sample holder, and the height of the sample stage is adjusted to 30mm using the sample height gauge.
[0197] The SEM equipment, observation method, and conditions are as described above. From the obtained SEM images, the average number of particles with the longest diameter w in a nearly planar plane is calculated using the image processing software ImageJ (developed by Wayne Rasband). The scale is set as described above, and the average number of particles with the longest diameter w in a nearly planar plane is calculated using the following procedure.
[0198] Select Set Measurements from the Analyze menu, then select Feret's Check the diameter option. Also, select ROI Manager from the Tools menu in Analyze, and check Show All and Labels in the newly opened ROI Manager window. Next, use the Elliptical Selections tool on the toolbar to approximate a roughly plane for one microparticle with an ellipse, as shown in Figure 8. With that done, select Add in the ROI Manager window. Similarly, for particles other than the selected particles, approximate the plane with an ellipse and select Add. After repeating the operation for all particles in the image, select Measure in the ROI Manager window to perform the analysis. From the newly opened Results window, obtain the longest diameter w (Feret) of the approximate plane of each microparticle. The longest diameter w of the approximate plane of the microparticle obtained in this way is the distance of the longest straight line connecting any two points on the outer perimeter of the approximate plane of the microparticle.
[0199] The above procedure is performed for 100 microparticles to be evaluated, and the average number of particles with the longest diameter w on the approximate plane is calculated.
[0200] <Method for calculating the average number of particles with a ratio of maximum height h to maximum width b h / b> The average value of the ratio h / b (maximum height h to maximum width b) is calculated using a scanning transmission electron microscope (STEM). The preparation of the sample for STEM observation, the STEM apparatus, the observation method, and the conditions are the same as those described in <Method for confirming that microparticles have both substantially flat and curved surfaces>. From the obtained STEM images, the average number of particles with a h / b ratio is calculated using the image processing software ImageJ (developed by Wayne Rasband). As mentioned above, the scale is set, and the subsequent procedure is as follows.
[0201] Select ROI Manager from the Tools menu in the Analyze menu, and check Show All and Labels in the newly opened ROI Manager window. Next, use the Straight Line tool on the toolbar to draw a straight line Ls1 that gives the maximum height h, as shown in Figures 5(a) to (c), in the same way as explained earlier. With that done, select Add in the ROI Manager window. Next, as shown in Figures 5(a) to (c), draw a line Ls2 that is perpendicular to the line Ls1 that gives the maximum height h and parallel to the virtual line Li. Line Ls2 is drawn such that the distance Dc between the two intersection points Pf and Pg where line Ls2 intersects with line Lc originating from the surface is maximized. The distance Dc between intersection points Pf and Pg is the maximum width b. Draw a line Ls2, select Add, and then select Measure in the ROI Manager window to perform the analysis. From the newly opened Results window, obtain the length corresponding to the maximum height h and maximum width b, and calculate the ratio h / b. The above procedure is performed for 100 microparticles to be evaluated, and the average number of the ratio h / b is calculated.
[0202] <Confirmation that the fine particles contain organosilicon compounds> Confirmation that the fine particles adhering to the outer surface of the developing roller of this disclosure contain organosilicon compounds is performed using a Fourier transform infrared spectrometer (FTIR). First, SEM carbon double-sided tape (manufactured by Nisshin EM Co., Ltd.) is attached to the sample stage, and a sufficient amount of fine particles adhering to the outer surface of the developing roller is collected using this double-sided tape to create the sample.
[0203] Next, the above sample is measured using an FTIR spectrometer (product name: FT / IR-4700, manufactured by JASCO Corporation) under the conditions of crystal: Ge, ATR method, and 64 integration cycles. From the obtained infrared spectrum, the presence of organosilicon compounds is confirmed by the presence or absence of signals caused by the following organic groups, for example: methyl group (Si-CH3), ethyl group (Si-C2H5), propyl group (Si-C3H7), butyl group (Si-C4H9), and pentyl group (Si-C5H) bonded to the silicon atom. 11 ), hexyl group (Si-C6H 13 ), heptyl group (Si-C7H 15 ), octyl group (Si-C8H 17 ), such alkyl groups
[0204] <Method for verifying the structure represented by equations (D), (T), and (Q)> Confirmation that the fine particles contain at least one selected from the group consisting of structures represented by formulas (D), (T), and (Q), and confirmation that the toner has silica particles as an external additive (having the structure represented by formula (Q)), is performed using a nuclear magnetic resonance spectrometer (NMR). Of the structures represented by formulas (D), (T), and (Q), the Ra, Rb, and Rc that are bonded to the silicon atom are as follows: 13 Confirmation is performed by 13C-NMR (solid-state) measurement. The measurement conditions are shown below. " 13 Measurement conditions for C-NMR (solid state) Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample: 150 mg of fine particles Measurement temperature: room temperature Pulse mode: CP / MAS Measurement nuclear frequency: 123.25MHz ( 13 C) Reference substance: Adamantane (external standard: 29.5ppm) Sample rotation speed: 20kHz Contact time: 2ms Delay time: 2 seconds Total number of times: 1024 In the structures represented by formulas (D), (T), and (Q), the presence of Ra, Rb, and Rc can be confirmed by the presence or absence of signals originating from the following organic groups: methyl group (Si-CH3), ethyl group (Si-C2H5), propyl group (Si-C3H7), butyl group (Si-C4H9), and pentyl group (Si-C5H) bonded to the silicon atom. 11 ), hexyl group (Si-C6H 13 ), heptyl group (Si-C7H 15 ), octyl group (Si-C8H 17 Alkyl groups such as ), aryl groups such as phenyl groups (Si-C6H5); alkylene groups such as methine groups (>CH-Si), methylene groups (Si-CH2-), ethylene groups (Si-C2H4-), trimethylene groups (Si-C3H6-); and arylene groups such as phenylene groups (Si-C6H4-).
[0205] Of the structures represented by formulas (D), (T), and (Q), the siloxane bond portion is as follows: 29 This was confirmed by Si-NMR (solid-state) measurement. The measurement conditions are shown below. " 29 Measurement conditions for Si-NMR (solid state) Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample: 150 mg of fine particles Measurement temperature: room temperature Pulse mode: CP / MAS Measured nuclear frequency: 97.38MHz ( 29 Si) Reference material: DSS (external standard: 1.534ppm) Sample rotation speed: 10kHz Contact time: 10ms Delay time: 2 seconds Cumulative number of times: 2000-8000
[0206] After the above measurements, the multiple silane components of the fine particles with different substituents and bonding groups are separated into peaks for structures X1, X2, X3, and X4 using curve fitting, and the peak area of each is calculated. The X1 structure represented by formula (1) is: (Rd)(Re)(Rf)SiO 1 / 2 The X2 structure represented by formula (2): (Rg)(Rh)Si(O 1 / 2 )2 The X3 structure represented by equation (3): RiSi(O 1 / 2 )3 X4 structure represented by formula (4): Si(O 1 / 2 )4 [ka]
[0207] (In formulas (1) to (4), Rd, Re, Rf, Rg, Rh, and Ri represent organic groups, halogen atoms, hydroxyl groups, acetoxy groups, or alkoxy groups bonded to the silicon atom.) In equations (1) to (4), the structures enclosed by the rectangles are the X1 structure to the X4 structure, respectively.
[0208] fine particles 29 In the chart obtained by Si-NMR measurement, the ratio of the peak areas of the X2 to X4 structures, which are attributed to the structures of formulas (D), (T), and (Q), to the total peak area of the organosilicon polymer is preferably 50 mol% or more, and more preferably 70 mol% or more.
[0209] Furthermore, if it is necessary to examine the structure represented by equations (D), (T), and (Q) in more detail, 13 C-NMR and 29 Along with the SiNMR measurement results 1 Identification may also be performed using the results of 1H-NMR measurements.
[0210] <Method for calculating the amount of fine particles on the outer surface of a surface layer to which fine particles are attached> The amount of fine particles on the outer surface of the surface layer to which the fine particles are attached can be measured by elemental analysis using EDS. Apply SEM carbon double-sided tape (manufactured by Nisshin EM Co., Ltd.) to the sample stage (aluminum sample stage 15mm x 6mm), and attach the sample, which has been cut from a developing roller with a razor, to the tape with the outer surface of the developing roller facing upwards. Deposit platinum onto the tape at 15mA for 15 seconds. Set the sample stage in the sample holder and adjust the height of the sample stage, including the attached developing roller piece, to 30mm using the sample height gauge.
[0211] Next, the outer surface of the developing roller is observed using a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.) in a field of view magnified up to 50,000 times. The outer surface of the developing roller is focused and observed. EDS analysis is performed on an arbitrary position on the outer surface of the developing roller to measure the elemental concentration (atomic%) of Si element on the outer surface of the developing roller containing fine particles. The elemental concentration of Si element is based on the concentration of all elements present on the outer surface of the surface layer of the developing roller.
[0212] The above measurement is repeated 10 times at different locations on the outer surface of the developing roller, and the arithmetic mean is obtained. Next, the sample is removed from the scanning electron microscope. The outer surface of the sample is then taped with mending tape MP-18 (Scotch), and the fine particles on the outer surface of the sample are peeled off. The sample from which the fine particles have been peeled off is again observed using a scanning electron microscope, with the outer surface of the developing roller magnified to a maximum of 50,000 times. The outer surface of the developing roller is focused and observed. EDS analysis is performed at a location in the observation field where no fine particles are present, and the elemental concentration (atomic%) of Si on the outer surface of the developing roller that does not contain fine particles is measured. The above measurement is repeated 10 times at different locations on the developing roller from which the fine particles have been peeled off, and the arithmetic mean is obtained. The difference between the arithmetic mean of the elemental concentration of Si on the outer surface of the developing roller containing the fine particles obtained in this way and the arithmetic mean of the elemental concentration of Si on the outer surface of the developing roller from which the fine particles have been removed is taken to calculate the amount of fine particles (atomic%) on the outer surface of the surface layer to which the fine particles are attached.
[0213] <Method for calculating the adhesion rate of silica particles and the amount of silica added by the water washing method> The adhesion rate of silica particles by the water washing method is calculated using the following method. The water washing method is as follows:
[0214] (washing with water) Add 160g of sucrose (manufactured by Kishida Chemical) to 100mL of deionized water and dissolve it while heating in a water bath to prepare a concentrated sucrose solution. Put 31g of the above concentrated sucrose solution into a centrifugal tube (capacity 50ml) and Contaminon N (nonionic surfactant, anionic surfactant, A 10% by mass aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of organic builders, Wako Pure Add 6 mL of (manufactured by Yakugyo Co., Ltd.) to prepare a dispersion. Add 1.0 g of toner to this dispersion. Use a spatula or similar tool to break up any clumps of toner. The centrifugation tube is shaken for 20 minutes using a shaker (MIGHTY SHAKER AS-1N, manufactured by AS ONE Corporation) at a shaking speed of 300 rpm and a shaking amplitude of 40 mm. After shaking, the solution is transferred to a 50 mL glass tube for a swing rotor and separated using a centrifuge (H-9R, manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 minutes. Visually confirm that the toner and aqueous solution have been sufficiently separated, and collect the toner separated to the top layer using a spatula or similar tool. Filter the aqueous solution containing the collected toner using a vacuum filter, and then dry it in a dryer for at least 1 hour. The dried toner is crushed with a spatula and washed with water to obtain a sample.
[0215] Next, the amount of silicon in the obtained water-washed sample is measured using X-ray fluorescence. The adhesion rate (%) is calculated from the ratio of the target element in the toner after washing and the toner before washing. The measurement of X-ray fluorescence for each element will conform to JIS K 0119-1969, specifically as follows: The measurement equipment used will be the wavelength-dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical) and the accompanying dedicated software "Super Q ver.4.0F" (manufactured by PANalytical) for setting measurement conditions and analyzing measurement data. Rh will be used as the anode of the X-ray tube, the measurement atmosphere will be vacuum, the measurement diameter (collimator mask diameter) will be 10 mm, and the measurement time will be 10 seconds. In addition, a proportional counter (PC) will be used for measuring light elements, and a scintillation counter (SC) will be used for measuring heavy elements. For the measurement sample, 1g each of toner before and after washing is placed in a dedicated 10mm diameter aluminum ring for pressing and leveled. Next, a pellet molded to a thickness of 2mm is used, which is then pressurized at 20MPa for 60 seconds using a tablet molding and compression machine "BRE-32" (manufactured by Maekawa Testing Machinery Co., Ltd.). Measurements are performed under the above conditions, and the element is identified based on the peak position of the obtained X-rays. The concentration is then calculated from the count rate (unit: cps), which is the number of X-ray photons per unit time.
[0216] For quantitative analysis of silicon in toner, 0.5 parts by mass of silica (SiO2) fine powder is added to 100 parts by mass of toner particles and thoroughly mixed using a coffee grinder. Similarly, 2.0 parts by mass and 5.0 parts by mass of silica fine powder are mixed with toner particles, respectively, and these are used as calibration samples.
[0217] For each sample, a pellet of the sample for calibration curve is prepared using a tablet molding compressor as described above, and the count rate (unit: cps) of Si-Kα rays observed at the diffraction angle (2θ) = 109.08° when PET is used as the spectroscopic crystal is measured. At this time, the acceleration voltage and current values of the X-ray generator are set to 24kV and 100mA, respectively. A linear calibration curve is obtained by plotting the obtained X-ray count rate on the vertical axis and the amount of SiO2 added to each calibration curve sample on the horizontal axis.
[0218] Next, the toner to be analyzed is pelletized using a tablet molding and compression machine as described above, and the counting rate of Si-Kα rays is measured. Then, the silica content in the toner is determined from the calibration curve described above. The ratio of the amount of silicon element W (after washing) of the toner after washing to the amount of silicon element W (before washing) of the toner before washing, calculated using the method described above, is determined and expressed as the adhesion rate (%).
[0219] Adhesion rate (%) = {Amount of silicon element W (before washing) - Amount of silicon element W (after washing)} / Amount of silicon element W (before washing) Furthermore, the amount of silica added as an external additive (parts by mass) can be calculated from the amount of silicon element W (before washing) of the toner measured at this time.
[0220] <Method for calculating the number-average particle size of primary silica particles> The analysis is performed using a combination of a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.) and elemental analysis by energy-dispersive X-ray spectroscopy (EDS). Sample preparation is as follows: A thin layer of conductive paste (product number 16053, manufactured by TED PELLA, Inc., PELCO Colloidal Graphite, Isopropanol base) is applied to the sample stage (aluminum sample stage 15mm x 6mm), and toner is then deposited on top of it. After removing excess toner from the sample stage by air blowing, platinum deposition is performed at 15mA for 15 seconds. The sample stage is then set in the sample holder, and the height of the sample stage is adjusted to 30mm using the sample height gauge.
[0221] Using a scanning electron microscope, the toner is observed in a field of view magnified up to 50,000 times. The external additive is observed by focusing on the surface of the toner particles. EDS analysis is performed on each particle of the external additive, and it is determined whether the analyzed particle is a silica particle based on the presence or absence of a Si element peak. In a field of view magnified up to 200,000 times, the elemental analysis method using EDS described above is used in conjunction with randomly capturing images of the outer surface of the toner. From the captured images, 100 silica particles are randomly selected, the major axis of the primary particles of the target microparticles is measured, and the arithmetic mean is defined as the number-average particle size.
[0222] If the toner contains both organosilicon polymer particles and silica particles, the silica particles are identified by comparing the ratio of the elemental content (atomic%) of Si and O (Si / O ratio) with that of a standard sample. EDS analysis was performed on standard samples of organosilicon polymer particles and silica particles under the same conditions to obtain the elemental content (atomic%) of Si and O, respectively.
[0223] Let A be the Si / O ratio of organosilicon polymer particles, and B be the Si / O ratio of silica particles. Select measurement conditions in which A is significantly larger than B. Specifically, ten measurements are taken on the standard sample under the same conditions, and the arithmetic mean values A and B are obtained. The measurement conditions are selected such that the obtained average value A / B > 1.1. If the Si / O ratio of the particle being identified is closer to A than [(A+B) / 2], then the particle is identified as an organosilicon polymer particle. Otherwise, it is identified as a silica particle. Tospar 120A (Momentive Performance Materials Japan LLC) is used as the standard for organosilicon polymer particles, and HDK V15 (Asahi Kasei) is used as the standard for silica microparticles. The observation magnification should be adjusted as appropriate depending on the size of the silica particles.
[0224] <Method for identifying hydrotalcite particles> The hydrotalcite particles, which are external additives, can be identified by combining shape observation using a scanning electron microscope (SEM) and elemental analysis using energy-dispersive X-ray spectroscopy (EDS). Using a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.), toner is observed in a field of view magnified up to 50,000 times. The toner particle surface is focused to observe the external additive to be identified. EDS analysis is performed on the external additive to be identified, and hydrotalcite particles can be identified from the type of elemental peaks. As elemental peaks, at least one metal selected from the group consisting of Mg, Zn, Ca, Ba, Ni, Sr, Cu, and Fe, which are metals that can constitute hydrotalcite particles, is an elemental peak. If elemental peaks of q and at least one metal selected from the group consisting of Al, B, Ga, Fe, Co, and In are observed, the presence of hydrotalcite particles containing the two types of metals can be inferred. A sample of hydrotalcite particles, inferred from EDS analysis, is prepared separately, and its shape is observed by SEM and then analyzed by EDS. The analysis results of the sample are compared with those of the target particle to determine whether or not it is a hydrotalcite particle.
[0225] <Method for measuring the elemental ratios of polyvalent metal elements in hydrotalcite particles> The elemental ratios of polyvalent metal elements in hydrotalcite particles are measured by toner EDS mapping using a scanning transmission electron microscope (STEM). EDS mapping provides spectral data for each pixel in the analysis area. By using a silicon drift detector with a large detection element area, EDS mapping can be measured with high sensitivity. By performing statistical analysis on the spectral data of each pixel obtained through EDS mapping measurements, it is possible to obtain principal component mappings by extracting pixels with similar spectra, enabling component-specific mapping.
[0226] The sample for observation is prepared using the following procedure. 0.5 g of toner is weighed and placed in an 8 mm diameter cylindrical mold. Using a Newton press, it is subjected to a load of 40 kN for 2 minutes to produce a cylindrical toner pellet with a diameter of 8 mm and a thickness of approximately 1 mm. A 200 nm thick thin section is prepared from the toner pellet using an ultramicrotome (Leica, FC7).
[0227] STEM-EDS analysis will be performed using the following equipment and conditions. Scanning transmission electron microscope; JEOL Ltd. JEM-2800 EDS detector; JEOL JED-2300T Dry SD100GV detector (detection element area: 100 mm²) 2 ) EDS analyzer; Thermo Fisher Scientific NORAN System 7 [Conditions for STEM-EDS] • STEM acceleration voltage: 200kV ·Magnification: 20,000x • Probe size 1nm
[0228] STEM image size: 1024 x 1024 pixels (to acquire EDS elemental mapping images at the same location). EDS mapping size: 256 x 256 pixels, Dwell time: 30 μs, Number of integrations: 100 frames The ratios of various elements, including polyvalent metal elements, in hydrotalcite particles, based on multivariate analysis, are determined as follows.
[0229] The EDS mapping is obtained using the STEM-EDS analyzer described above. Next, the collected spectral mapping data is subjected to multivariate analysis using the COMPASS (PCA) mode in the NORAN System 7 measurement command described above, and a principal component map image is extracted. The settings should be as follows: • Kernel size: 3x3 • Quantitative map setting: High (slow) • Filter fit type: High precision (slow) Simultaneously, this operation calculates the area ratio of each extracted principal component within the EDS measurement field. The EDS spectra obtained from each principal component mapping are then subjected to quantitative analysis using the Cliff-Lorrimer method.
[0230] The distinction between toner particles and hydrotalcite particles is made based on the quantitative analysis results of the obtained STEM-EDS main component mapping. Hydrotalcite particles can be identified based on particle size, shape, content of polyvalent metals such as aluminum and magnesium, and their respective ratios. Furthermore, if fluorine and aluminum are present inside the hydrotalcite particles by the following means, the particles can be determined to be hydrotalcite particles containing fluorine and aluminum.
[0231] (Analysis method for fluorine and aluminum in hydrotalcite particles) Based on the mapping data obtained by STEM-EDS mapping analysis using the method described above, we will analyze the fluorine and aluminum content of hydrotalcite particles. Specifically, we will perform EDS line analysis in the direction normal to the outer circumference of the hydrotalcite particles to analyze the fluorine and aluminum present inside the particles. A schematic diagram of the line analysis is shown in Figure 9(a). Line analysis is performed on the toner particle 91 and the hydrotalcite particle 93 adjacent to the toner particle 92, in the direction normal to the outer circumference of the hydrotalcite particle 93, i.e., in the direction of 95. Note that 94 indicates the boundary of the toner particle. Select the area containing hydrotalcite particles in the acquired STEM image using the rectangular selection tool, and perform line analysis under the following conditions. Line analysis conditions STEM magnification: 800,000x Line length: 200nm Line width: 30nm Number of line divisions: 100 points (intensity measured every 2 nm)
[0232] If the elemental peak intensity of fluorine or aluminum is 1.5 times or more than the background intensity in the EDS spectrum of hydrotalcite particles, and the elemental peak intensity of fluorine or aluminum at both ends of the hydrotalcite particle in line analysis (points a and b in Figure 9(a)) does not exceed 3.0 times the peak intensity at point c, then it is determined that the element is contained inside the hydrotalcite particle. Point c is defined as the midpoint of line segment ab (i.e., the midpoint of both ends mentioned above). Examples of X-ray intensities of fluorine and aluminum obtained by line analysis are shown in Figures 9(b) and 9(c). When hydrotalcite particles contain fluorine and aluminum internally, the X-ray intensity graph normalized by peak intensity shows the shape shown in Figure 9(b). When hydrotalcite particles contain fluorine derived from the surface treatment agent, the X-ray intensity graph normalized by peak intensity shows peaks near points a and b at both ends of the fluorine graph, as shown in Figure 9(c). By confirming the X-ray intensities derived from fluorine and aluminum in line analysis, it is possible to confirm that hydrotalcite particles contain fluorine and aluminum internally.
[0233] (Method for calculating the ratio of the atomic concentration of fluorine to aluminum (elemental ratio) F / Al in hydrotalcite particles) The ratio of the atomic number concentration of fluorine to aluminum in hydrotalcite particles (F / Al), obtained from the principal component mapping derived from hydrotalcite particles using the aforementioned STEM-EDS mapping analysis, is acquired in multiple fields of view. The arithmetic mean of these values for 100 or more particles is then taken to obtain the ratio of the atomic number concentration of fluorine to aluminum in hydrotalcite particles (F / Al).
[0234] (Method for calculating the ratio of magnesium to aluminum atomic concentration (elemental ratio) Mg / Al in hydrotalcite particles) Using the same method as described above for calculating the ratio of atomic concentrations of fluorine to aluminum (elemental ratio) F / Al in hydrotalcite particles, the same procedure is performed for magnesium and aluminum to calculate the ratio of atomic concentrations of magnesium to aluminum (elemental ratio) Mg / Al in hydrotalcite particles.
[0235] <Method for measuring the number-average particle size of primary hydrotalcite particles> The number-average particle size of hydrotalcite particles is measured using a scanning electron microscope "S-4800" (product name; manufactured by Hitachi, Ltd.) and elemental analysis by energy-dispersive X-ray spectroscopy (EDS). Sample preparation is as follows: A thin layer of conductive paste (product number 16053, manufactured by TED PELLA, Inc., PELCO Colloidal Graphite, Isopropanol base) is applied to the sample stage (aluminum sample stage 15mm x 6mm), and toner is then deposited on top of it. After removing excess toner from the sample stage by air blowing, platinum deposition is performed at 15mA for 15 seconds. The sample stage is then set in the sample holder, and the height of the sample stage is adjusted to 30mm using the sample height gauge.
[0236] Using the elemental analysis method by EDS described above, the outer surface of the toner is randomly photographed in a field of view magnified up to 200,000 times. Hydrotalcite particles are selected from the captured images, and the major axis of 100 randomly selected primary hydrotalcite particles is measured to determine the number-average particle size. The observation magnification is adjusted as appropriate depending on the size of the external additive. Here, particles that appear as a single particle during observation are judged to be primary particles. [Examples]
[0237] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, the "parts" in the following formulations refer to mass.
[0238] <Example of developing roller manufacturing> [Manufacturing of developing roller 1] (Manufacturing of the intermediate layer roller 1) As a base, a SUS304 axial core with an outer diameter of 6 mm and a length of 263 mm was prepared by applying a primer (product name: DY35-051, manufactured by Toray Dow Corning Co., Ltd.) and baking it. This base was placed in a mold, and an addition-type silicone rubber composition, which was a mixture of the materials shown in Table 1 below, was injected into the cavity formed in the mold. Next, the mold was heated to cure the addition-type silicone rubber composition at 150°C for 15 minutes, and then demolded. After that, the curing reaction was completed by further heating at 180°C for 1 hour, producing an intermediate layer roller 1 having a conductive elastic layer (intermediate layer 22) with a thickness of 2.75 mm on the outer circumference of the substrate. [Table 1]
[0239] (Manufacturing of isocyanate-terminated prepolymer B-1) Under a nitrogen atmosphere, 100 parts of polyether polyol (product name: PTG-L3500, manufactured by Hodogaya Chemical Co., Ltd.) were gradually added dropwise to 25 parts of polymeric MDI (product name: Millionate MR200, manufactured by Tosoh Corporation) in a reaction vessel. During this time, the temperature inside the reaction vessel was maintained at 65°C. After the dropwise addition was complete, the reaction was allowed to proceed at 65°C for 2 hours. The resulting reaction mixture was cooled to room temperature to obtain isocyanate-terminated prepolymer B-1, which has an isocyanate group content of 4.3% by mass.
[0240] (Preparation of resin coating solution X-1) Next, the raw materials were mixed according to the proportions shown in Table 2 below. [Table 2] Next, methyl ethyl ketone (MEK) was added to the above raw materials so that the solid content was 30% by mass, and mixed solution 1 was obtained. Furthermore, 250 parts of mixed solution 1 and 200 parts of glass beads with an average particle size of 0.8 mm were placed in a 450 mL glass bottle and dispersed for 3 hours using a paint shaker (manufactured by Toyo Seiki Co., Ltd.). After that, the glass beads were removed to obtain resin layer coating liquid X-1 for forming a resin layer containing cross-linked urethane resin.
[0241] (Fabrication of resin layer roller Y-1) After dipping the intermediate layer roller 1 once into the surface layer coating liquid X-1, it was air-dried at 23°C for 30 minutes. Then, it was dried for 1 hour in a hot air circulating dryer set to 160°C to produce a resin layer roller Y-1 in which a resin layer containing crosslinked urethane resin was formed on the outer surface of the intermediate layer roller. At this time, the thickness of the resin layer was 15 μm. The dipping time for coating was 9 seconds. The dipping and lifting speed was adjusted so that the initial speed was 20 mm / sec and the final speed was 2 mm / sec. Between / sec and 2mm / sec, the velocity was changed linearly with respect to time.
[0242] (Preparation of impregnation coating solution W-1) The raw materials were mixed according to the following proportions. Acrylic monomer G-1 (product name: NK Ester A-NPG, manufactured by Shin-Nakamura Chemical Co., Ltd.): 100.0 parts Photopolymerization initiator H-1 (product name: Omnirad184, manufactured by IGM Resins): 10.0 parts Next, methyl ethyl ketone (MEK) was added to the above raw materials so that the solid content was 5.5% by mass, and the mixture was stirred on a rotating machine for 3 hours to obtain impregnation coating solution W-1.
[0243] (Preparation of developing roller 1) The impregnation coating liquid W-1 was dipped once into the resin layer roller Y-1 to impregnate it, and then air-dried at 90°C for 60 minutes. The dipping and lifting speed was 20 mm / sec. Next, while rotating the resin layer roller Y-1 circumferentially at 20 rpm, a high-pressure mercury UV lamp (product name: Handy Type UV Curing Device, manufactured by Mario Network Co., Ltd.) was used in an air atmosphere to cure the surface with an integrated light intensity of 15,000 mJ / cm². 2 UV light was irradiated onto the outer surface of the resin layer roller Y-1 to crosslink and cure the acrylic monomer. In this manner, the impregnated developing roller 1 was manufactured. The thickness of the surface layer was 15 μm. The physical properties of the resulting developing roller 1 are shown in Table 5.
[0244] [Manufacturing examples of developing rollers 2-5, C-1, and C-2] Table 3 shows the raw materials used in the manufacture of developing rollers 2-5, C-1, and C-2. [Table 3]
[0245] Resin layer rollers Y-2 to Y-4 were formed in the same manner as resin layer roller Y-1, except that the solid content of the resin layer coating and the dipping application and pulling speed were adjusted to achieve a layer thickness of 15 μm, according to the formulation shown in Table 4. [Table 4]
[0246] Developing rollers 2-5, C-1, and C-2 were manufactured according to the formulation and manufacturing conditions shown in Table 5, while the other rollers were manufactured in the same manner as developing roller 1. The physical properties of the obtained developing rollers are shown in addition to Table 5. The layer thickness of developing rollers 2-5, C-1, and C-2 was 15 μm. [Table 5] NV% indicates the mass percentage of solids.
[0247] <Examples of fine particle manufacturing> [Example of manufacturing of microparticle 1] (Preparation step of precursor aqueous solution 1) 60.0 parts of deionized water were weighed into a reaction vessel equipped with a stirrer and thermometer, and the pH was adjusted to 3.0 using 10% by mass hydrochloric acid. This was heated while stirring to a temperature of 60°C. Then, 40.0 parts of methyltrimethoxysilane were added and the mixture was stirred for 2 hours. After visually confirming that the oil and water layers had not separated and had become a single layer, the mixture was cooled to obtain precursor aqueous solution 1.
[0248] (Polymerization process) In a reaction vessel equipped with a stirrer and thermometer, 1000.0 parts of deionized water were weighed, 6.0 parts of Neugen EA177 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and 380.0 parts of PMMA particles (non-crosslinked, average particle size 10 μm) were added. The mixture was heated while stirring at 180 rpm, and the temperature was maintained at 50°C for 30 minutes. While continuing to stir, 34.0 parts of precursor aqueous solution 1 were added. After holding the mixture for 30 minutes, the pH was adjusted to 9.0 using an aqueous sodium hydroxide solution. The mixture was then held for another 300 minutes to form substantially hemispherical microparticles made of organosilicon polymer on the surface of the PMMA particles.
[0249] (Washing process) After the polymerization process was complete, the reaction solution was cooled and solid-liquid separation was performed using a pressure filter to obtain a cake of PMMA particles with fine particles formed. This was then reslurred with deionized water to obtain a dispersion again. The mixture was then subjected to solid-liquid separation again using a filter. After repeating the slurry separation and solid-liquid separation several times, a cake of PMMA particles with fine particles formed was finally obtained by solid-liquid separation.
[0250] (separation, drying process) After the washing process was completed, the PMMA particle cake, in which fine particles had formed, was added to 1000.0 parts of acetone in a reaction vessel equipped with a stirrer and held for 1 hour while stirring at 180 rpm. After visually confirming that the PMMA particles were sufficiently dissolved, the mixture was centrifuged at 15,000 rpm for 10 minutes, the precipitate was collected, and vacuum drying was performed. The mixture was then crushed using a pulverizer (Hosokawa Micron Corporation), and substantially hemispherical fine particles were separated using an air classifier to obtain substantially hemispherical fine particles 1 having both a roughly flat and a curved surface. The physical properties of the obtained fine particles 1 are shown in Table 7.
[0251] [Manufacturing examples of particulate matter 2-6, C-1, and C-2] Fine particles 2-6, C-1, and C-2 were obtained according to the formulation and manufacturing conditions shown in Table 6, and otherwise in substantially the same manner as the manufacturing example of fine particle 1, which has a hemispherical shape. The physical properties of the obtained fine particles 2-6, C-1, and C-2 are shown in Table 7. [Table 6]
[0252] [Example of manufacturing of particulate matter C-3] (first step) In a reaction vessel equipped with a thermometer and a stirrer, 360.0 parts of water were added, and 15.0 parts of 5.0% by mass hydrochloric acid were added to form a homogeneous solution. While stirring at a temperature of 25°C, 136.0 parts of methyltrimethoxysilane were added, and after stirring for 5 hours, the mixture was filtered to obtain a clear reaction solution containing a silanol compound or a partial condensate thereof.
[0253] (Second process) In a reaction vessel equipped with a thermometer, stirrer, and dropping device, 440.0 parts of water were added, and 17.0 parts of 10.0% by mass aqueous ammonia were added to form a homogeneous solution. While stirring at a temperature of 35°C, add 100.0 parts of the reaction solution obtained in the first step for 0.5 hours. The solution was added dropwise and stirred for 6 hours to obtain a suspension. The obtained suspension was centrifuged to allow the fine particles to settle and were then removed. These particles were dried in a dryer at 200°C for 24 hours to obtain fine particles C-3. The obtained fine particles C-3 were spherical and had no flat (end faces). For the spherical fine particles C-3, the average number of particles with the longest diameter was measured using the same method as described above for any projection plane w. This is shown in Table 7 as the w value for fine particles C-3.
[0254] [Example of manufacturing of particulate matter C4] Fine talc powder (product name: P-8, manufactured by Nippon Talc Co., Ltd.) was used as the fine particle C-3. The fine talc powder was flattened. Using the measurement method for w of the fine talc powder described above, the average number of the longest diameter particles on the flattened surface of the fine talc powder was measured. This is shown in Table 7 as w for the fine talc powder. [Table 7]
[0255] <Example of toner supply roller manufacturing> [Manufacturing example of toner supply roller 1] A cylindrical member with an inner diameter of 13 mm, coated with a mold release agent on its inner surface, an upper die member, and a lower die member were used as mold components. A core made of stainless steel (SUS304) with an outer diameter of 5 mm and a length of 254 mm was placed in the mold as the base. Materials (A), (B), (E) to (I) listed below were blended, and the resulting urethane rubber composition was injected into the cavity formed inside the mold.
[0256] (A): Ionic conductive agent (lithium bis(trifluoromethanesulfonyl)imide, trade name: EF-N115, manufactured by Mitsubishi Materials Corporation): 5.0 parts (B): Polyol (polyethylene propylene ether triol with a number-average molecular weight of 2000, trade name: Actcol EP-550N; manufactured by Mitsui Chemicals): 100.0 parts (E): Polyisocyanate blend (containing NCO%=45, MDI=20%, trade name: Cosmonate™20; manufactured by Mitsui Chemicals, Inc.): 24.4 parts (F): Silicone foam stabilizer (product name: SRX274C, manufactured by Toray Dow Corning): 1.0 part (G): Tertiary amine catalyst (bis(2-dimethylaminoethyl) ether and dipropylene Recall mixture, product name: TOYOCAT-ET, manufactured by Tosoh Corporation): 0.3 parts (H): Amine catalyst B (product name: TOYOCAT-L33, manufactured by Tosoh Corporation): 0.2 parts (I): Foaming agent (water): 1.4 parts Next, the mold was heated to 70°C, and the urethane rubber composition was foamed and cured for 10 minutes. The substrate, with a foamed elastic layer formed on its circumferential surface, was then demolded from the mold. In this way, a toner supply roller according to Example 1 was produced, having a foamed elastic layer with a diameter of 16.5 mm on the outer circumference of the substrate.
[0257] [Manufacturing example of toner supply roller 2] (A): The toner supply roller 2 was manufactured in the same manner as the manufacturing example of the toner supply roller 1, except that an ionic conductive agent was not used.
[0258] [Manufacturing example of toner supply roller 3] (A): The toner supply roller 3 was manufactured in the same manner as the manufacturing example of toner supply roller 1, except that the ion conductive agent was changed to lithium perchlorate (manufactured by Nippon Carlit Co., Ltd.): 5.0 parts.
[0259] <Examples of toner manufacturing> [Example of toner particle 1 manufacturing] (Preparation process of aqueous media) 14.0 parts sodium phosphate (manufactured by Rasa Industries, dodecahydrate) was added to 1000.0 parts deionized water in a reaction vessel, and the temperature was maintained at 65°C for 1 hour while purging with nitrogen. Using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), a calcium chloride aqueous solution, prepared by dissolving 9.2 parts calcium chloride (dihydrate) in 10.0 parts deionized water, was added all at once while stirring at 12000 rpm to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 10% by mass hydrochloric acid was added to the aqueous medium to adjust the pH to 6.0 to obtain an aqueous medium.
[0260] (Preparation process for polymerizable monomer composition) • Styrene: 60.0 parts CI Pigment Blue 15:3 : 6.5 parts The above materials were placed in an attritor (manufactured by Mitsui Miike Chemical Machinery Co., Ltd.), and then dispersed using 1.7 mm diameter zirconia particles at 220 rpm for 5 hours to prepare a pigment dispersion. The following materials were added to this pigment dispersion. • Styrene: 11.0 parts n-butyl acrylate: 29.0 parts Crosslinking agent (divinylbenzene): 0.2 parts • Saturated polyester resin: 6.0 parts (A condensation polymer of propylene oxide-modified bisphenol A (2 molar adduct) and terephthalic acid (molar ratio 10:12), glass transition temperature Tg = 68°C, weight-average molecular weight Mw = 10000, molecular weight distribution Mw / Mn = 5.12) Fischer-Tropsch wax (melting point 78°C): 10.0 parts • Charge control agent: 0.5 part (Aluminum compound of 3,5-di-tert-butylsalicylic acid) This was kept warm at 65°C, and uniformly dissolved and dispersed at 500 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to prepare a polymerizable monomer composition.
[0261] (granulation process) While maintaining the temperature of the aqueous medium at 70°C and the rotation speed of the stirring device at 12,000 rpm, a polymerizable monomer composition was added to the aqueous medium, and 9.0 parts of t-butyl peroxypivalate, a polymerization initiator, were added. Granulation was then carried out for 10 minutes while maintaining the rotation speed of the stirring device at 12,000 rpm.
[0262] (Polymerization process) The stirrer was changed from a high-speed stirring device to one with propeller blades, and polymerization was carried out for 5 hours while stirring at 150 rpm and maintaining a temperature of 70°C. Then, the temperature was raised to 95°C and heated for 5 hours to carry out the polymerization reaction and obtain a slurry of toner particles.
[0263] (Washing and drying process) After the polymerization process was complete, the toner particle slurry was cooled, and the pH of the system was adjusted to 1.5 or less by adding hydrochloric acid to the toner particle slurry. After stirring for 1 hour, solid-liquid separation was performed using a pressure filter to obtain the toner cake. The toner cake was re-slurred with deionized water to obtain a dispersion again, and then solid-liquid separation was performed again using a pressure filter. The re-slurrying and solid-liquid separation process was repeated until the electrical conductivity of the filtrate was 5.0 μS / cm or less, and finally, solid-liquid separation was performed to obtain the toner cake.
[0264] The obtained toner cake was dried using an airflow dryer, a flash jet dryer (manufactured by Seishin Corporation), and then the finer particles were removed using a multi-part classifier utilizing the Coanda effect to obtain toner particles 1. The drying conditions were an inlet temperature of 90°C, a dryer outlet temperature of 40°C, and the toner cake supply rate was adjusted according to the moisture content of the toner cake to ensure that the outlet temperature did not deviate from 40°C. The weight-average particle size of the obtained toner particles 1 was 6.2 μm.
[0265] [Example of Toner 1 production] (External addition process) Toner 1 was obtained by mixing the following materials in a Henschel mixer (FM-10 model, manufactured by Nippon Coke Industries Co., Ltd.). • Toner particle ratio: 1 / 100.0 parts • Silica particles 2 (product name: NX90S, manufactured by Nippon Aerosil Co., Ltd.): 1.5 parts Furthermore, the Henschel mixer's stirring blade rotation speed was set to 3,600 rpm, the mixing time to 5 minutes, and the jacket temperature to 10°C. The obtained toner mixture 1 was sieved through a mesh with an opening of 109 μm to obtain toner 1.
[0266] [Example of silica particle production] In a hexane solution containing 10 parts hexamethyldisilazane and 20 parts dimethylpolysiloxane (product name: KF-96-100cs, manufactured by Shin-Etsu Chemical Co., Ltd.), raw silica nanoparticles (product name: Aerosil 380, manufactured by Nippon Aerosil Co., Ltd., raw material BET specific surface area 380 m²) obtained by gas-phase oxidation and high-temperature calcination were mixed. 2100 parts of ( / g) were added and hydrophobic treatment was performed at 350°C. After treatment, crushing was performed using a pin mill at a peripheral speed of 70 m / sec, and further classification was performed to adjust the particle size, resulting in silica particles 1 (average primary particle size 7 nm, measured BET specific surface area 300 m²). 2 / g) was obtained.
[0267] Table 8 shows the silica particles used as external additives. The average particle size in the table refers to the number-average particle size of the primary particles. [Table 8]
[0268] [Example of hydrotalcite particle 1 production] A mixed aqueous solution of 1.03 mol / L magnesium chloride and 0.239 mol / L aluminum sulfate (Solution A), an aqueous solution of 0.753 mol / L sodium carbonate (Solution B), and an aqueous solution of 3.39 mol / L sodium hydroxide (Solution C) were prepared. Next, solutions A, B, and C were added to the reaction vessel using a metering pump at a flow rate such that the volume ratio of solution A to B was 4.5:1. Solution C was used to maintain the pH of the reaction mixture in the range of 9.3 to 9.6, and the reaction was carried out at a temperature of 40°C to produce a precipitate. After filtration and washing, the mixture was re-emulsified with deionized water to obtain the hydrotalcite slurry. The hydrotalcite concentration in the obtained hydrotalcite slurry was 5.6% by mass.
[0269] The obtained hydrotalcite slurry was vacuum-dried overnight at 40°C. Next, the dried hydrotalcite was added to deionized water to a concentration of 0.1% (w / v%). The mixture was stirred at a constant rate for 48 hours using a magnetic stirrer, to the extent that sedimentation did not occur. Afterward, the mixture was filtered through a 0.5 μm pore size membrane filter and washed with deionized water. The obtained hydrotalcite was vacuum-dried overnight at 40°C and then subjected to crushing treatment. The composition and properties of the obtained hydrotalcite particles 1 are shown in Table 9.
[0270] [Example of hydrotalcite particle 2 production] A hydrotalcite slurry was obtained in the same manner as in the production example of hydrotalcite particle 1. The obtained hydrotalcite slurry was vacuum-dried overnight at 40°C. NaF was dissolved in deionized water to a concentration of 100 mg / L, and a solution was prepared by adjusting the pH to 7.0 using 1 mol / L HCl or 1 mol / L NaOH. Dried hydrotalcite was added to this solution to a concentration of 0.1% (w / v%). The mixture was stirred at a constant speed for 48 hours using a magnetic stirrer, to the extent that sedimentation did not occur. After that, the mixture was filtered through a membrane filter with a pore size of 0.5 μm and washed with deionized water. The obtained hydrotalcite was vacuum-dried overnight at 40°C and then subjected to crushing treatment. The composition and physical properties of the obtained hydrotalcite particle 2 are shown in Table 9.
[0271] [Examples of manufacturing hydrotalcite particles 3 and 4] Hydrotalcite particles 3 and 4 were obtained in the same manner as in the production example of hydrotalcite particles 2, except that the concentrations of Solution A, Solution B, and the NaF aqueous solution were conveniently adjusted. The composition and physical properties of the obtained hydrotalcite particles 3 and 4 are shown in Table 9. Note that the average particle size in the table refers to the number-average particle size of the primary particles. [Table 9]
[0272] [Manufacturing examples for toners 2-12 and C-1] In the manufacturing example of Toner 1, Toners 2-12 and C-1 were obtained in the same manner as in the manufacturing example of Toner 1, except that the type of silica particles, the type of hydrotalcite particles, the amount added, the rotation speed of the stirring blade during external mixing, the mixing time, and the jacket temperature were changed as shown in Table 10. Table 10 shows the silica particle adhesion rate for each toner. Note that the number of parts added in the table represents parts by mass per 100 parts by mass of toner particles. [Table 10]
[0273] <Example of a developing device manufacturing process> [Manufacturing example of developing device 1] (Manufacturing process of developing roller 1A with fine particles 1 attached to its outer surface) After removing the existing toner from the developer unit of the process cartridge (product name: CE411A Cyan, manufactured by Hewlett-Packard), 30g of fine particles 1 were filled in. Next, the existing developer roller was removed from the developer unit, and developer roller 1 was installed. After that, the sealing material was removed from the developer unit.
[0274] Then, the process cartridge having the above-mentioned developing device was installed in an electrophotographic device (product name: LaserJetPro400color, manufactured by Hewlett-Packard), and paper was passed through it for 30 minutes to adhere fine particles 1 to the outer surface of the developing roller 1. After feeding the paper, the developing roller 1 was removed from the developing device, and excess fine particles 1 were removed by air blowing to produce a developing roller 1A with fine particles 1 attached to its outer surface. Table 11 shows the amount of fine particles 1 attached to the outer surface of the developing roller 1A produced under the same conditions.
[0275] (Manufacturing process of developing device 1) The developing unit was removed from an unused process cartridge (CE411A Cyan, manufactured by Hewlett-Packard). Next, the existing toner was removed from the developing device, and then 50g of toner 1 was added. Furthermore, the existing developing roller, developing blade, and toner supply roller were removed from the developing apparatus, and the toner supply roller 1 was installed. After installing the existing developing blade in the same position as before removal, the developing roller 1A, on which the fine particles 1 were attached to the outer surface, was installed, and the developing apparatus 1 was manufactured.
[0276] [Manufacturing examples of developing equipment 2-28, C-1-C-7] In the manufacturing example of developing apparatus 1, developing apparatuses 2 to 28 and C-1 to C-7 were manufactured in the same manner as in the manufacturing example of developing apparatus 1, except that the paper feeding time in the process of adhering fine particles to the outer surface of the developing roller was appropriately changed, and the developing roller, fine particles, toner supply roller, and toner were changed as shown in Table 11. The amount of fine particles in the developing roller 1 having fine particles 1 on its outer surface manufactured under each condition is shown in Table 11. Note that developing rollers 1A-5A, C-1A, and C-2A are developing rollers to which fine particles have been attached as described in Table 11, respectively, to developing rollers 1-5, C-1, and C-2.
[0277] Furthermore, the developing rollers in developing devices 1-29, C-1-C-4, and C-7 had multiple fine particles attached to their outer surfaces. In addition, the substantially flat surfaces of each of the fine particles attached to the outer surfaces of the developing rollers in developing devices 1-29, C-1-C-4, and C-7 were in surface contact with the outer surface of the surface layer of the developing roller, and each of the fine particles formed a convex portion on the outer surface of the surface layer, with at least a portion of the convex portion being composed of a curved surface. On the other hand, no such nearly flat surfaces or convex portions were observed in the developing rollers of developing devices C-5 and C-6. [Table 11] In the table, the amount of adhesion represents the amount of fine particles on the outer surface of the surface layer of the developing roller to which the fine particles have adhered, and atm.% indicates atomic%.
[0278] <Example 1> The following evaluation was performed on developing device 1. The evaluation results are shown in Table 12.
[0279] [Evaluation of band images after prolonged exposure to high temperature and high humidity] Developing device 1 was left in a 40°C, 95% RH environment for 30 days. Next, after removing the developing device 1 from the above environment, the developing device is placed in the process cart. The components were assembled onto a ridge and left for 24 hours in a 23°C, 55% RH environment. Next, the process cartridge with the developing device 1 assembled was left in a 30°C, 80% RH environment for 24 hours. Next, under the same conditions, the sealing material was removed from the developing unit 1 and mounted on the image forming apparatus (product name: LaserJetPro400color, manufactured by HP). After the image forming apparatus was powered on and the initial sequence was executed, the evaluation images shown below were output in succession, and the band image was evaluated. (Evaluation image) • Halftone image: 1 sheet (first sheet in continuous paper feed) • 18 images of solid white backgrounds • Halftone image: 1 sheet (20th sheet in continuous printing) • 19 images of solid white background • Halftone image: 1 sheet (40th sheet in continuous printing) • 19 images of solid white background • Halftone image: 1 sheet (60th sheet in continuous printing) • 19 images of solid white background • Halftone image: 1 sheet (80th sheet in continuous printing) • 19 images of solid white background • Halftone image: 1 sheet (100th sheet in continuous printing)
[0280] (Image evaluation of the band) The band image of the developing roller pitch was evaluated using the following evaluation criteria for each halftone image obtained from the continuous paper feeding described above. Rank A: No developing roller pitch band is visible on the image. Rank B: A very slight band of development roller pitch is visible on the image. Rank C: A slight band of development roller pitch is visible on the image. Rank D: The developing roller pitch band is clearly visible on the image.
[0281] <Examples 2-29, Comparative Examples 1-7> Except for changing developing apparatus 1 to developing apparatuses 2-29 and C-1-C-7, the strip images were evaluated after being left in a high-temperature, high-humidity environment for a long period of time, in the same manner as in Example 1. The evaluation results for Examples 2-29 and Comparative Examples 1-7 are shown in Table 12.
[0282] [Table 12] As shown in Table 12, according to one embodiment of the present disclosure, even with a developing roller in which only the vicinity of the outermost surface is hardened, the band image was quickly recovered by the initial sequence and image output even after being left in a high-temperature, high-humidity environment for a long period of time, and a high-quality image was obtained.
[0283] This disclosure relates to the following configuration and method. (Composition 1) A developing apparatus comprising a developing roller, toner, and a toner supply roller for supplying the toner to the developing roller, The developing roller is A conductive substrate, A single surface layer on the substrate, It has, The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2): E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The adhesion rate of the silica particles to the toner particles, as measured by the water washing method, is 50% or more. A developing apparatus characterized by the following features. (Configuration 2) When observing the cross-section of the fine particles intersecting the substantially plane, Let Pa and Pb be the two intersection points of the line Lf originating from the approximate plane and the line Lc originating from the curved surface, and let the line connecting Pa and Pb be the imaginary line Li. In a line Ls1 that intersects the virtual line Li perpendicularly, let Pc be the intersection point of the virtual line Li and the line Ls1, let Pe be the intersection point of the line Lc and the line Ls1, and let Da be the distance between the intersection point Pc and the intersection point Pe. Let Db be the distance between the intersection point Pd and the intersection point Pe of line Lf and line Ls1. The maximum height h is defined as the distance when either Da or Db is at its maximum. In a line Ls2 parallel to the virtual line Li, let Pf and Pg be the two intersection points where line Ls2 and line Lc intersect, and let the maximum width b be the distance at which the distance Dc between Pf and Pg is maximized. The average value of the ratio of the maximum height h to the maximum width b, h / b, is between 0.30 and 0.80. The developing apparatus described in Configuration 1. (Composition 3) The developing apparatus according to configuration 1 or 2, wherein the amount of fine particles on the outer surface of the surface layer to which the fine particles are attached, as measured by elemental analysis of the outer surface of the surface layer to which the fine particles are attached, is 3.0 atomic% or more. (Composition 4) A developing apparatus according to any one of configurations 1 to 3, wherein the number-average particle size of the primary particles of the silica particles is 7 to 400 nm. (Composition 5) The developing apparatus according to any one of configurations 1 to 4, wherein the content of the silica particles is 0.5 to 3.0 parts by mass per 100 parts by mass of the toner particles. (Composition 6) The toner supply roller comprises a conductive substrate and a foamed elastic layer on the substrate. The foamed elastic layer contains an ionic conductive agent, The developing apparatus according to any one of configurations 1 to 5, wherein the toner further comprises hydrotalcite particles as an external additive. (Composition 7) The aforementioned ionic conductive agent contains fluorine as an anionic component, The developing apparatus according to configuration 6, wherein fluorine is present inside the hydrotalcite particles in line analysis during STEM-EDS mapping analysis of the toner. (Composition 8) In line analysis of the STEM-EDS mapping analysis of the toner, fluorine and aluminum were found to be present inside the hydrotalcite particles. The ratio of the atomic concentration of fluorine to aluminum in the hydrotalcite particles, F / Al, obtained from the main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is 0.01 to 0.60. A developing apparatus as described in configuration 6 or 7. (Method 9) A cleaning method for cleaning the outer surface of a developing roller on which multiple fine particles are attached to the outer surface, The developing roller has a conductive substrate and a single-layer surface layer on the substrate. The surface layer has a matrix containing crosslinked urethane resin as a binder. Let E1 be the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2), E1 ≥ 200 MPa ···(1) 10MPa ≤ E2 ≤ 100MPa ···(2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The cleaning method is The process includes supplying toner to the developing roller using a toner supply roller, and bringing into contact with a plurality of fine particles adhering to the outer surface of the surface layer the toner to remove the fine particles from the outer surface of the surface layer, The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, A cleaning method characterized in that the adhesion rate of the silica particles to the toner particles, as measured by a water washing method, is 50% or more. (Composition 10) A process cartridge that is detachably attached to the main body of an electrophotographic image forming apparatus, Having a developing apparatus as described in any of configurations 1 to 8, A process cartridge characterized by the following features. (Composition 11) An electrophotographic image forming apparatus having a photoreceptor and a developing device that supplies a developer to an electrostatic latent image formed on the photoreceptor, The developing apparatus is the developing apparatus described in any of configurations 1 to 8. An electrophotographic image forming apparatus characterized by the following:
Claims
1. A developing apparatus comprising a developing roller, toner, and a toner supply roller for supplying the toner to the developing roller, The developing roller is A conductive substrate, A single surface layer on the substrate, It has, The surface layer has a matrix containing crosslinked urethane resin as a binder. E1 is defined as the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2): E1 ≥ 200 MPa ... (1) 10 MPa ≤ E2 ≤ 100 MPa ... (2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, The adhesion rate of the silica particles to the toner particles, as measured by the water washing method, is 50% or more. A developing apparatus characterized by the following features.
2. When observing the cross-section of the fine particles intersecting the substantially plane, Let Pa and Pb be the two intersection points of the line Lf originating from the approximate plane and the line Lc originating from the curved surface, and let the line connecting Pa and Pb be the imaginary line Li. In a line Ls1 that intersects the virtual line Li perpendicularly, let Pc be the intersection point of the virtual line Li and the line Ls1, let Pe be the intersection point of the line Lc and the line Ls1, and let Da be the distance between the intersection point Pc and the intersection point Pe. Let Db be the distance between the intersection point Pd and the intersection point Pe of line Lf and line Ls1. The maximum height h is defined as the distance when either Da or Db is at its maximum. In a line Ls2 parallel to the virtual line Li, let Pf and Pg be the two intersection points where line Ls2 and line Lc intersect, and let the maximum width b be the distance at which the distance Dc between Pf and Pg is maximized. The average value of the ratio of the maximum height h to the maximum width b, h / b, is between 0.30 and 0.
80. The developing apparatus according to claim 1.
3. The developing apparatus according to claim 1, wherein the amount of fine particles on the outer surface of the surface layer to which the fine particles are attached, as measured by elemental analysis of the outer surface of the surface layer to which the fine particles are attached, is 3.0 atomic% or more.
4. The developing apparatus according to claim 1, wherein the number-average particle size of the primary particles of the silica particles is 7 to 400 nm.
5. The developing apparatus according to claim 1, wherein the content of the silica particles is 0.5 to 3.0 parts by mass per 100 parts by mass of the toner particles.
6. The toner supply roller comprises a conductive substrate and a foamed elastic layer on the substrate. The foamed elastic layer contains an ionic conductive agent, The developing apparatus according to claim 1, wherein the toner further comprises hydrotalcite particles as an external additive.
7. The aforementioned ionic conductive agent contains fluorine as an anionic component, The developing apparatus according to claim 6, wherein fluorine is present inside the hydrotalcite particles in line analysis in STEM-EDS mapping analysis of the toner.
8. In line analysis of the STEM-EDS mapping analysis of the toner, fluorine and aluminum were found to be present inside the hydrotalcite particles. The ratio of the atomic number concentration of fluorine to aluminum in the hydrotalcite particles, F / Al, obtained from the main component mapping of the hydrotalcite particles by STEM-EDS mapping analysis of the toner, is between 0.01 and 0.
60. The developing apparatus according to claim 7.
9. A cleaning method for cleaning the outer surface of a developing roller on which multiple fine particles are attached to the outer surface, The developing roller has a conductive substrate and a single-layer surface layer on the substrate. The surface layer has a matrix containing crosslinked urethane resin as a binder. E1 is defined as the elastic modulus of the matrix in a first region from the outer surface of the surface layer to a depth of 0.1 μm, as measured in a cross-section in the thickness direction of the surface layer. When the elastic modulus of the matrix in the second region from the outer surface to a depth of 1.0 μm to 1.1 μm is E2, E1 and E2 satisfy the following equations (1) and (2), E1 ≥ 200 MPa ... (1) 10 MPa ≤ E2 ≤ 100 MPa ... (2) Multiple fine particles are attached to the outer surface of the surface layer, and these fine particles form protrusions on the outer surface of the surface layer. Each of the fine particles contains an organosilicon compound, In a cross-sectional view of the fine particles and their outer surface, each of the fine particles has a substantially flat surface that contacts the outer surface of the surface layer and a curved surface that constitutes at least a part of the protrusion. The average number of the longest diameter w of the substantially planar surface of the fine particles is 10 to 400 nm. The cleaning method is The process includes supplying toner to the developing roller using a toner supply roller, and bringing into contact with a plurality of fine particles adhering to the outer surface of the surface layer the toner to remove the fine particles from the outer surface of the surface layer, The toner comprises toner particles and silica particles as an external additive. The toner particles contain a binder resin, A cleaning method characterized in that the adhesion rate of the silica particles to the toner particles, as measured by a water washing method, is 50% or more.
10. A process cartridge that is detachably attached to the main body of an electrophotographic image forming apparatus, A developing apparatus according to any one of claims 1 to 8, A process cartridge characterized by the following features.
11. The device comprises a photoreceptor and a developing apparatus that supplies a developer to the electrostatic latent image formed on the photoreceptor. An electrophotographic image forming apparatus, The developing apparatus is the developing apparatus described in any one of claims 1 to 8. An electrophotographic image forming apparatus characterized by the following:
Citation Information
Patent Citations
Positively charged toner for developing electrostatic charge image
JP1991236064A
Developing roller with porous inorganic particle attached thereto, electrophotographic process cartridge, and electrophotographic image forming apparatus
JP2008304845A
Developing roller, electrophotographic process cartridge, and electrophotographic image forming apparatus
JP2010128348A
Toner supply roller
JP2010134255A
Conductive foam roll for electrophotographic apparatus
JP2016186510A